Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Associations between early pregnancy essential metals and birth outcomes: Exploration of effect modification by maternal thyroid hormones - Xiao-Yu Zhao; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Molecular bridging stabilizes halide perovskites for durable photocatalytic H2 production in pure water - Xiwen Ma; Na Han; Wanying Cheng; Guiqiang Diao; Ming Sun; Shaomin Peng; Guichuan Xing; Lin Yu (Chemical Engineering Journal, 2026)

SERS sensing platform based on MIL-100(Fe)@AgNPs for norepinephrine/adenosine monitoring in patient plasma - Peng Zhao; Kai Liu; Yueyan Li; Xiaofang Ban; Yuheng Wu; Jiaqi Liu; Xiaohong Wu; Ziyi Cheng; Fan Wang; Shuo Li; Feng Lin; Huifang Tang; et al. (Analytica Chimica Acta, 2026)

Thermal evolution of biomarker profiles in the Ordovician biodegraded reservoirs of the Tabei Uplift, Tarim Basin, northwestern China: implications from closed-system thermal simulation experiments - Yuwei Yang; Yuhong Liao; Yijun Zheng; Yueyi Huang; Bin Cheng; Huanyu Lin; Yunpeng Wang; Ping’An Peng (Journal of Asian Earth Sciences, 2026)

Basalt fabric functionalized with Copper/Silver nanoparticles as a salt-tolerant solar evaporator for all-weather brackish water desalination - Dilibinuer Niyazimaimaiti; Ying-Lin He; Zhuo Chen; Anand Parkash; Jincheng Wu; Ghizlane Achagri; Chun-Hong Zhou; Yuan Fan; Wen-Rui Ma; Peng-Cheng Ma; Abudukeremu Kadier (Journal of Environmental Chemical Engineering, 2026)

Recent progress on hydrogen production via catalytic Auto-thermal methane Reforming: A focus on catalysts and operational parameters - Jun Wan; Peng Liu; Feiyi Zhou; Huajie Lyu; Teng Hu; Keyu Cheng; Yihong Song; Jiabiao Zou; Xiao Zhang; Saisai Lin; Chenghang Zheng; Xiang Gao (Fuel, 2026)

Source apportionment of PM2.5-bound elemental carbon via stable carbon isotope analysis: A comparison study with receptor model - Cheng Wang; Yulong Yan; Xiaolin Duan; Dongmei Hu; Jiaqi Dong; Ning Jin; Hao Chen; Lin Peng (Environmental Pollution, 2026)

See and destroy bacterial spores: Visual detection and in situ inactivation using a terbium-porphyrin nanoplatform - Shan Sun; Ke Cheng; Jiayi Feng; Hongbo Juan; Kefeng Zhou; Mingyan Zhao; Heng Zhang; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2026)

Hydraulic conductivity and the associated xylem anatomy as reliable predictors of tree productivity for Populus species along the fast-slow spectrum - Attaullah Khan; Xue-Wei Gong; Jing-Jing Guo; Cheng-Lin Yuan; Shen-Hao Song; Zhong-Yi Pang; Yan-Hui Peng; Xue-Kai Sun; Guang-You Hao (Agricultural and Forest Meteorology, 2026)

Palmitic acid-evoked PKR/JNK activation and SIRT1 decline: Association with myocardial ageing phenotype changes and partial reversal by inhibitors - Wenxi Li; Guoshun Liu; Shuijin Huang; Tianhai Lin; Cheng Peng; Feng Liu (Tissue and Cell, 2026)

Soil microplastics as carriers of organic pollutants: Sorption mechanisms and environmental behavior - Jinghao Peng; Binyan Cheng; Lin Jiang; Qian Du (Science of The Total Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Seismic reflection profiles reveal the Changjiangbu Fault and shallow structural features in the Ying-Yun Sag, northeastern Jianghan Basin - Cong Jin; Song Lin; Xiaohu Deng; Daicheng Peng; Fei Cheng (Journal of Applied Geophysics, 2026)

Comprehensive analysis of microbial community assembly and metabolic dynamics reveals the effects of environmental acidity on flavor formation pathways during the Zhejiang rosy vinegar fermentation process - Cheng-Hao Jin; Yong-Zhu Zhang; Wen-Tian Song; Peng Wang; Chang-Ling Wu; Lin-Mei Liang; Wei Feng; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2026)

Associations of prenatal individual and mixture per- and polyfluoroalkyl substances (PFAS) exposures with fetal growth trajectories: Modifying effects of maternal micronutrient status - Zhen-Hua Li; Hai-Yang Weng; Chun-Yong Wang; Xiao-Yu Zhao; Guo-Peng Gao; Kai Huang; Mao-Lin Chen; Fang-Biao Tao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2026)

Identifying critical windows and sex-specific effects of periconceptional exposure to fine particulate matter and temperature on fetal growth trajectories: A longitudinal birth cohort study - Si-Wei Dai; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Xiao-Yu Zhao; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Neuronal and Glial YAP/TAZ in the Spinal Cord Contribute to the Development of Bone Cancer Pain in Mice - Bo Peng; Xiaqing Lin; Jiang-Jian Hu; Huabao Liao; Cheng Li; Zhaoyu Li; Xue-Jun Song (Neuroscience Bulletin, 2026)

Artificial Intelligence and Protein Design: A retrospective study on 20-year emerging trends and core research areas from bibliometric perspectives - Wenjuan Zhao; Xiuwu Pan; Wei Yang; Zichang Liu; Xiyi Wei; Anqi Lin; Bufu Tang; Lin Zhang; Mingjia Xiao; Qing Zeng; Quan Cheng; Weiming Mou; et al. (Probiotics and Antimicrobial Proteins, 2026)

Trophic plasticity drives species-specific adaptive responses to seasonal variability in reef-building corals - Xiao-Lei Yu; Lei Jiang; Yong Luo; Lin-Tao Huang; Peng Zhang; Zhan-Wei Li; Cheng-Yue Liu; Pan Zhang; Jian-Yu Chen; Sheng Liu; Gui-Xin Dong; Hui Huang (Coral Reefs, 2026)

Elucidating targets and mechanisms of dietary mycotoxin carcinogenesis via network toxicology, pan-cancer analysis, and molecular simulation - Peng Lin; Wei Cheng; Xin Qi; Jing Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

A comprehensive review on the chemical composition, pharmacological effects and quality evaluation of Gentiana straminea Maxim. - Yuan-Wen Zhuang; Min Wang; Jian-Tao Zhao; Yu-Qing Wang; Run-Qian Yu; Huan Xia; Xiao-Hong Wei; Peng-Cheng Lin; Gui-Yang Xia; Sheng Lin (Journal of Natural Medicines, 2026)

Effect of Excavation Sequence and Bolt Support on Surrounding-Rock Stability of a Double-Tunnel System in Jointed Rock Mass - Feng Jiang; Tian-lin Huang; Hai-zhen Huang; Ji-song Wang; Peng He; Gang Wang; Chun-gui Li; Ting-fang Liu; Cheng-cheng Zheng; Zhi-yong Xiao (Applied Geophysics, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Transcarotid Artery Revascularization for Asymptomatic Carotid Stenosis: A Systematic Review and Meta-Analysis - Zhi-Cheng Jiang; Qi-Fei Hu; Jia-Ming Huang; Xian-Wei Wang; Tong Lin; Xi-Lin Gao; Jia-Wen Cui; Jing-Lin Zhao; Dong Chen; Shu-Peng Li (Translational Stroke Research, 2026)

Portable smartphone-assisted fluorescence platform based on dual-excitation nitrogen-doped carbon dots for simultaneous detection of chlorogenic acid and tinidazole - Junyuan Shi; Zihang Yin; Dejin Lin; Dingfeng Wang; Siting Peng; Wendi Xiao; Houwen Hu; Jiong Cheng; Da Chen (Analytica Chimica Acta, 2026)

DOM-mediated inhibition of ciprofloxacin photodegradation: Dual roles of antioxidant quenching and triplet-state interactions - Jihong Xu; Weiwen Sun; Jiayan Ding; Yong Huang; Xi Chen; Lin Li; Cheng Peng; Lushi Lian; Xiaohong Guan (Water Research, 2026)

Non-radical PMS activation for simultaneous nitrite and sulfamethoxazole removal with inhibited nitrobyproduct formation - Jiawei Lin; Wenjun Zhou; Jiaqi Peng; Yongyou Hu; Hongfeng Zhang; Cheng Zhao; Qi Shan; Hao Zhou; Yi Yin (Journal of Water Process Engineering, 2026)

Windows of susceptibility and the modifying role of residential greenness in the association between prenatal exposure to non-optimal temperatures and infant BMIZ trajectories - Zhen-Hua Li; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Xiao-Yu Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Hierarchical biomass-derived carbon microtubes for SiOx@C anodes for lithium storage - Qiuqi Li; Dong Xie; Zhenya Liu; Zhaoqing Lin; Tengyang Liu; Shoushan Wang; Peng Liu; Shilei Xie; Min Zhang; Faliang Cheng (Chemical Engineering Journal, 2026)

Impact of air pollution control strategies on full-phase chlorine species emissions from coal-fired power plants in China during 2013-2022 - Yuying Tang; Yulong Yan; Xionghui Qiu; Zhijian Li; Manli Wang; Zhen Li; Minneng Wen; Wenyi Jin; Yuyang Cheng; Lin Peng (Atmospheric Environment, 2026)

Why does tropical cyclone Emeraude move along a small annular track? - Yaoyao Zhou; Lixiang Shen; Ziqiong Cheng; Lin Peng; Rufa’i Isyaku; Haibin Lü (Journal of Earth System Science, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Functional divergence of two ethylene receptor subfamilies in calcium permeability - Chenliang Pan; Junyuan Cheng; Zining Lin; Dongdong Hao; Zhina Xiao; Yuhang Ming; Peng You; Hongtao Yu; Wei Yan; Wen Song; Li Liu; Hongwei Guo (Molecular Plant, 2026)

A distributed monitoring method for soil water content based on actively heated optical frequency domain reflectometry and physics-informed neural networks - Lin Cheng; Wenqi Gao; Dongyan Jia; Junrui Chai; Hao Peng; Xiao Han (Journal of Hydrology, 2026)

Uncovering the dynamic role of bedrock-stored water in ecosystem evapotranspiration - Yang Qiu; Fawang Zhang; Lin Gao; Zekang He; Hanxiang Xiong; Ling Peng; Zhiye Wang; Hao Cui; Cheng Su; Defang Zhang; Shizheng Zhou; Chuanming Ma; et al. (Journal of Hydrology, 2026)

Al-doped α-MnO2 for low-temperature catalytic oxidation of formaldehyde - Zhengnan Lin; Zhao Zheng; Junchen Li; Cheng Zhang; Qingyan Fang; Peng Tan; Gang Chen (Journal of Environmental Chemical Engineering, 2026)

Enhanced brackish water desalination performance of 3D invasive plant wood-based evaporator via coupled photo-thermal and Joule-heating effect - Chun-Hong Zhou; Ying-Lin He; Zhuo Chen; Dilibinuer Niyazimaimaiti; Jincheng Wu; Yuan Fan; Amanula Yimingniyazi; Peng-Cheng Ma; Abudukeremu Kadier (Desalination, 2026)

Rab10 GTPase from the mud crab Scylla paramamosain is involved in the host immune response against V. parahaemolyticus infection - Chang-Hong Cheng; Hai-Peng Qin; Si-Gang Fan; Hong-Ling Ma; Guang-Xin Liu; Dong-Lin Yao; Wen-Fan Luo; Xian-Feng Yang; Zhi-Xun Guo (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

African swine fever virus pNP419L inhibits host translation and increases viral replication through the PERK/eIF2α pathway - Xueying Wang; Zixuan Wang; Yilin Guo; Sai Niu; Rui Liang; Lin Cheng; Hakimeh Baghaei Daemi; Guiqing Peng (Veterinary Microbiology, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Fine-tuned Ce electron density directs H2O2 activation pathway in industrially employable CeO2 nanozymes for ∼100% specificity and boosted activity in (Bromo)peroxidase mimicking - Tianqi Cheng; Bo Yuan; Chao Zhao; Zicong Tan; Xinyu Wu; Jian Lin Chen; Juan Liu; Yufei Zhao; Hui Wei; Yung-Kang Peng (Chemical Engineering Journal, 2026)

Differences in priming effect of topsoil versus subsoil depends on ecosystem type - Lei Tao; Liming Yin; Feike A. Dijkstra; Junjie Lin; Peng Wang; Weixin Cheng (CATENA, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Hybridization and incomplete lineage sorting characterize the evolutionary history of two East Asian clades of Stewartia (Theaceae) - Han-Yang Lin; Miao Sun; Jian-Jun Jin; Cheng-Xin Fu; Douglas E. Soltis; Pamela S. Soltis; Yun-Peng Zhao (Molecular Phylogenetics and Evolution, 2026)

Transboundary dispersion and deposition of gaseous radioactive iodine revealed by anthropogenic 129I in mountainous regions - Yanyun Wang; Jie Zhou; Mu Lin; Yukun Fan; Peng Cheng; Luyuan Zhang; Huan Jiang; Ning Chen; Qi Liu; Ge Xu; Xiaolin Hou (Journal of Hazardous Materials, 2026)

Dominant governing mechanisms of deformation-seepage and dynamic evolution model of permeability in gas-containing coal under coupled stress-pore pressure - Chongzhi Wang; Bin Zhou; Shugang Li; Haifei Lin; Haiqing Shuang; Dongming Zhang; Shoujian Peng; Liang Cheng; Han Yang (Fuel, 2026)

Unveiling the effect of polymer-selective interactions with perovskite nanomaterials on the transport of microplastics in saturated porous media - Lin Xu; Xiaopeng Min; Jiacheng Zhang; Yanan Liu; Hyunjung Kim; Cheng Peng; Li Cai (Chemical Engineering Journal, 2026)

Pilot study on integrating multidisciplinary technologies to implement an autonomous and smart harvester for asparagus - Joe-Air Jiang; Jen-Cheng Wang; Hung-Jen Lin; Cheng-Ying Chou; Chia-Chun Chien; Wei-Hao Huang; An-Chi Liu; Cheng-Chun Lee; Ming-Chi Guo; Jui-Chu Peng (Computers and Electronics in Agriculture, 2025)

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Volcanic sulfur dioxide monitored from a constellation of FengYun hyperspectral infrared sounders in dawn-dusk, mid-morning, and afternoon sun-synchronous orbits - Zhao-Cheng Zeng; Lieven Clarisse; Bruno Franco; Cathy Clerbaux; Nicolas Theys; Chengli Qi; Lu Lee; Lin Zhu; Xiuqing Hu; Mingjian Gu; Peng Zhang (Remote Sensing of Environment, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Advances in the research on phenolic acids and flavonoids in vinegar: Sources, formation and degradation mechanisms, and functional properties - Cheng-Hao Jin; Yong-Zhu Zhang; Feng-Hua Wu; Chang-Ling Wu; Peng Wang; Wei Feng; Lin-Mei Liang; Wei-Jiang Xu; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2025)

New insight into the formation mechanism of key aroma compounds in the micro-pressure stewed duck meat: A volatilomics and lipidomics-based approach - Lei Zhao; Lin Li; Pi Li; Peng Gao; Jiangtao Xing; Chengyu Zeng; Cheng Li; Wanmei Wu; Daohong Zhang; Huan Liu (Food Research International, 2025)

Differential modulation of aroma profiles in instant Oolong tea powder by two Aspergillus niger β-glucosidases - Ziyue Chen; Qi Lin; Cheng Peng; Kunpeng Yu; Yanling Lin; Shuyi Weng; Lijun Li; Hui Ni; Feng Chen (Food Chemistry, 2025)

Tartary buckwheat-soy protein isolate composite gels: gelling, rheological, water-retention, and texture characteristics at different ratios - Xiao Han; Gen Ma; Lin Wang; Ting Cheng; Yangyang Guo; Liangzhen Jiang; Yan Wan; Xiaoqin Zheng; Changying Liu; Lianxin Peng; Gang Zhao; Xiulan Guo; et al. (Food Hydrocolloids, 2025)

Copper sulfide catalysts facilitating zinc sulfide electro-oxidation in aqueous zinc–sulfur batteries - Peng Hei; Guangxu Hu; Lin Yu; Yulai Lin; Xueying Ning; Bo Li; Yuqing Wang; Zhaohui Chen; He Chong; Hao Cheng; Jing Wang; Weibin Cui; et al. (Chemical Engineering Journal, 2025)

Research progress on chemical composition, pharmacological activity and clinical application of Panax japonicus - Ye Huang; Wen-yue Ning; Cai-e Wang; Peng-cheng Lin; Min Wang; Xian-hua Meng (Natural Product Research, 2025)

Early Cenozoic source to sink relation between the Tula Basin and the surrounding ranges: Insights for the Tibetan Plateau growth - Jingzhen Peng; Feng Cheng; Dehai Zhang; Hongwei Zhou; Maomao Wang; Xiangzhong Li; Zhaojie Guo; A. K. Khudoley; A. S. Tesakov; Lin Wang; Yan Ma (Science China Earth Sciences, 2025)

How the Carbon Neutrality Process Moves Forward: a Global-scale Evaluation from Past To Future - Yicheng Yang; Zefeng Qi; Hongxuan Fu; Shuan Peng; Nihed Benani; Xi Cheng; Jian Lin Chen; Pingjian Yang; Guozhu Mao (International Journal of Environmental Research, 2025)

Characterization of neutral fluids in the volcanic geothermal system under the Tatun Volcano Group, Taiwan - Yi-Chia Lu; Chyi Wang; Sheng-Rong Song; Pei-Ling Wang; Ting-Jui Song; Sachihiro Taguchi; Tsung-Ren Peng; Li-Hung Lin; Jian-Cheng Lee; Hong-Chun Li (Journal of Geochemical Exploration, 2025)

Unlocking biochar's carbonyl group: Fe-Mn oxide synergy enables high-efficiency As(III) immobilization via non-radical oxidation - Zihang Cheng; Yilin Wu; Ruiqi Du; Mingming Lin; Jingzi Beiyuan; Juan Liu; Peng Liu; Bowen Li; Xueding Jiang; Hailong Wang (Journal of Environmental Management, 2025)

Associations between prenatal exposure to air pollution and infant growth trajectories in the first two years: Exploring potential sexual dimorphism and sensitive windows - Zhen-Hua Li; Si-Wei Dai; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2025)

Topography-engineered cobalt-based microparticles for biofilm-eradicating medical device disinfection: Overcoming antibacterial resistance through mechano-bactericidal action - Ke Cheng; Shan Sun; Wenhao Zheng; Heng Zhang; Henggang Wang; Shang Gao; Si Li; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2025)

Platinum-copper nanocubezyme facilitate spinal cord recovery via synchronously alleviating oxidative stress and mitigating BNIP3-mediated mitochondrial dysfunction - Xiangge Liu; Cheng Peng; Huiyi Yang; Jiajun Deng; Ping Wu; Yongchun Xiao; Li Wan; Ke Wang; Guowei Zhang; Hua Yang; Jianyu Zou; Judun Zheng; et al. (Chemical Engineering Journal, 2025)

A novel vortexing-driven droplet digital CRISPR (VTD-CRISPR) platform for rapid and absolute quantitative detection of genetically modified crops - Jingzheng Chi; Yuzhen Wei; Jiannan Chen; Lin Ding; Xiaoyun Chen; Xiaofu Wang; Junfeng Xu; Cheng Peng (Chemical Engineering Journal, 2025)

Formoterol, a clinically approved drug, inhibits ferroptosis by suppressing lipid peroxidation and attenuates APAP-induced acute liver injury - Lin-Song Teng; Zhen-Dong Ying; Xiao-Han Sun; Hao-Cheng Hou; Shi-Dong Qiu; Peng Liu; Ke-Jing Li; Lei Zhang; Xie-Huang Sheng (Chemico-Biological Interactions, 2025)

Three-dimensional material point analysis of the Guanghua landslide influenced by topographic constraints - Yi-Pin Peng; Kuo-Hsin Yang; Wei-Lin Lee; Tatag Yufitra Rus; Shih-Hao Cheng; Jyun-Yen Wang; Chihping Kuo (Landslides, 2025)

Crop sample prediction and early mapping based on historical data: Exploration of an explainable FKAN framework - Feifei Cheng; Bingwen Qiu; Peng Yang; Wenbin Wu; Qiangyi Yu; Jianping Qian; Bingfang Wu; Jin Chen; Xuehong Chen; Francesco N. Tubiello; Piotr Tryjanowski; Viktoria Takacs; et al. (Computers and Electronics in Agriculture, 2025)

A full-ring mechanical model of shield tunnels considering detailed joint configurations - Si-Qi Yang; Huai-Na Wu; Hong-Zhan Cheng; Dong-Lin Feng; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Unveiling the multifaceted efficacy of Gu Sui Bu in osteoporosis treatment: insights from a zebrafish model and advanced analytical approaches - Wen-Ying Lin; Cheng-Huan Peng; Ming-Der Lin (Phytochemistry Letters, 2025)

Simulation and prediction of vertical migration of Cd²⁺ in heavy metal-contaminated soils amended with different passivators via Hydrus-1D - Ying Luo; Zhe Wang; Cheng-xia Wang; Jia-Qian Zhang; Kai Ye; Chao-liang Peng; Yi-ming Chen; Zhen-Long Zhang; Wen-xue Lin; Jing-yan Zhang; Shao-qin Chen (Journal of Environmental Chemical Engineering, 2025)

Mechanical performance analysis of fully grouted bolts considering yield and hardening characteristics - Akang Li; Hua Cheng; Zhongwen Yue; Chuanxin Rong; Peng Wang; Jian Lin (International Journal of Rock Mechanics and Mining Sciences, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

A novel hydrogel electrolyte for self-powered sensing and safe energy storage systems in extreme environments - Wen Jiang; Yang Tao; Qiuxiang Yang; Yudong Wang; Lin Peng; Ce Zhang; Shounian Cheng; Jiandan Liang; Yu Han; Xia Cao (Chemical Engineering Journal, 2025)

High-performance and robust 3D perovskite solar cells enabled by self-assembled amphiphilic molecules - Chao-Yun Lin; Guan-Lin Chen; Kuang-Hao Cheng; Syang-Peng Rwei; Hsiao-Chi Hsieh; Leeyih Wang (Chemical Engineering Journal, 2025)

Multi-channel thermal conductive phosphor-in-glass film with a record laser power density threshold for laser lighting - Hao Cheng; Yang Wang; Jiuzhou Zhao; Qing Wang; Shisheng Lin; Jiaxin Liu; Yun Mou; Lei Nie; Mingxiang Chen; Zhen Zhang; Yang Peng; Daqin Chen (Chemical Engineering Journal, 2025)

Pediatric Abdominal and Pelvic CT Scans and the Subsequent Risk of Malignancy and Benign Genital Tumors: A Retrospective Cohort Study - Feng-Yi Su; Chih-Feng Chen; Kevin Chih-Yang Huang; Cheng-Li Lin; Fuu-Jen Tsai; Jui-Ting Hsu; Shin-Lei Peng (Journal of Medical and Biological Engineering, 2025)

A Large Bioenergy Potential from the Third-Generation Bioenergy Crop Microalgae on Abandoned Croplands in China - Peng Cheng; Fengsong Pei; Tingting Kang; Junjie Wang; Kuiqi Yang; Lin Mao (BioEnergy Research, 2025)

A novel multifunctional suction-controlled apparatus for investigating tensile strength of unsaturated soils - Xiang-Shen Fu; Han-Lin Wang; Ren-Peng Chen; Cheng-Shuang Yin; Yue-Hui Sun; Xiao-Hu Zhang; Daniel Dias (Transportation Geotechnics, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Efficient removal of trace diazepam via enhanced peroxymonosulfate activation by 1T-phase and sulfur vacancy-rich MoS2-C-Fe - Jiawei Lin; Hongfeng Zhang; Jingyu Liu; Yongyou Hu; Jiaqi Peng; Feng Xu; Cheng Zhao; Qing Wang; Hao Zhou; Yi Yin (Journal of Cleaner Production, 2025)

Aeration causes lordosis in largemouth bass and blunt snout bream and identification of the associated genes - Haijie Chen; Leyang Peng; Jing Wang; Cheng Luo; Hui Qiao; Guili Song; Shimei Lin; Yong Long (Aquaculture, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

P2 purinergic receptors regulate the progression of colorectal cancer - Wen-jun Zhang; Li-peng Zhang; Si-jian Lin; Cheng-yi Wang; Yi-guan Le (Purinergic Signalling, 2025)

Humic acid-supported nanoscale zero-valent iron for sustainable cadmium remediation and crop safety in farmland soil - Yangzhi Liu; Dongren Zhou; Peng Huang; Chenghu Yang; Jing Zhang; Honghui Wang; Qilu Cheng; Yingxia Liu; Chengxiang Gao; Jinchuan Ma; Hui Lin; Junwei Ma (Journal of Hazardous Materials, 2025)

Application of artificial intelligence in the rapid determination of moisture content in medicine food homology substances - Mengyu Zhang; Boran Lin; Shudi Zhang; Cheng Peng; Chang Li; Tingting Feng; Lian Li; Aoli Wu; Chunguo Yang; Wentian Wang; Shouyao Huang; Lei Nie; et al. (Food Chemistry, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

A novel and sustainable invasive plant wood-based solar interfacial evaporator for efficient brackish water desalination - Chun-Hong Zhou; Ying-Lin He; Zhuo Chen; Yuan Fan; Amanula Yimingniyazi; Peng-Cheng Ma; Abudukeremu Kadier (Desalination, 2025)

Oil Film Detection for Marine Radar Image Using SBR Feature and Adaptive Threshold - Yulong Yang; Jin Yan; Jin Xu; Xinqi Zhong; Yumiao Huang; Jianxun Rui; Min Cheng; Yuanyuan Huang; Yimeng Wang; Tao Liang; Zisen Lin; Peng Liu (Journal of Marine Science and Engineering, 2025)
Marine oil spills pose a serious and persistent threat to marine ecosystems, coastal resources, and global environmental health. These incidents not only disrupt ecological balance by damaging marine flora and fauna but also lead to long-term economic consequences for fisheries, tourism, and maritime industries. Owing to their rapid spread and often unpredictable occurrence, timely and accurate detection is essential for effective containment and mitigation. An efficient detection system can significantly enhance the responsiveness of emergency teams, enabling targeted interventions that minimize ecological damage and economic loss. This paper proposes a marine radar-based oil spill detection method that combines the Significance-to-Boundary Ratio (SBR) feature with an improved Sauvola adaptive thresholding algorithm. The raw radar data was firstly preprocessed through mean and median filtering, grayscale correction, and contrast enhancement. SBR features were then employed to extract coarse oil spill regions, which were further refined using an improved Sauvola thresholding algorithm followed by a denoising step to obtain fine-grained segmentation. Comparative experiments using different threshold values demonstrate that the proposed method achieves superior segmentation performance by better preserving oil spill boundaries and reducing background noise. Overall, the approach provides a robust and efficient solution for marine oil spill detection and monitoring.

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Geothermal gas geochemistry in Southeast Tibetan Plateau margin influenced by magma chambers and fractures - Jia-Yi Wu; Hai Gang Cao; Peng Cheng Zhao; Yu Ping Guo; Xue-Gang Chen; Xiaohu Li; Jui-Fen Tsai; Pei-Ling Wang; Li-Hung Lin (Journal of Volcanology and Geothermal Research, 2025)

New insights into the impact of microplastics on nitrogen transformation in urban rivers based on field experiments - Cheng Yang; Yuanyuan Feng; Jinjiang Duan; Nayin Li; Qingping Zou; Peng Lin; Mengli Chen; Jiang Li; Han Zhang (Journal of Environmental Chemical Engineering, 2025)

A novel non-genetic strategy to increase lipid content in Phaeodactylum tricornutum - Kun-Tao Peng; Bing-Hong Xiong; Gao Cheng; Yuan-Hong Zhong; Lin Yu (Food Bioscience, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

Cost-effective production of squalene using Yarrowia lipolytica via metabolic engineering and fermentation engineering - Wen-Bo Lin; Hong Chen; Ze-Qi Song; Yu-Qing Pan; Peng-Cheng Hu; Xiao-Na Yang; Xiang-Yang Lu; Yun Tian; Hu-Hu Liu (Biotechnology Letters, 2025)

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

Identification of dietary protein utilization traits related SNPs and genes in brown-marbled grouper (Epinephelus fuscoguttatus) - Jin Zhang; Qinxi Dai; Yaorong Wang; Qianhao Wei; Cheng Peng; Yuqing Yang; Jinxiong Huang; Yanhua Huang; Jinhui Wu; Haoran Lin; Danqi Lu; Yong Zhang; et al. (Aquaculture, 2025)

Comprehensive analysis of microplastics at typical outlets around Hainan Island: From spatial distribution to flux estimation and correlation analysis - Shiyu Xie; Yuanyuan Su; Dan Qi; Fei Liu; Liu Gao; Ruiqi Bao; Xing Cheng; Xubing Lin; Tingting Zhang; Licheng Peng (Water Research, 2025)

Online monitoring of water quality in industrial wastewater treatment process based on near-infrared spectroscopy - Cheng Peng; Zeming Wu; Shudi Zhang; Boran Lin; Lei Nie; Weilu Tian; Hengchang Zang (Water Research, 2025)

Metabolic and microbial functionality during the fermentation of traditional Amaranth stems: Insights from metagenomics, flavoromics, and metabolomics - Qi Peng; Shuangqi Cheng; Jiahao Lin; Huajun Zheng; Guangfa Xie (Food Chemistry, 2025)

How the dispersion and coalescence behaviors of CO2 bubbles affecting carbonation reaction in bubble column reactor: experimental and numerical simulation study - Lin Chen; Jintao Ma; Cheng Chen; Xin Wang; Yonghong Qin; Enze Li; Yanxia Guo; Ran Peng; Zihe Pan (Chemical Engineering Journal, 2025)

Genotyping and antimicrobial susceptibility of Aeromonas veronii isolated from aquatic animals in Sichuan, China - Kun Peng; Silu Tian; Longjun Deng; Yu Yuan; Zixuan Cheng; Tiancai Li; Keyu Zhou; Jingyi Lin; Yi Geng (Antonie van Leeuwenhoek, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Quantitational life cycle assessment of Effluent-Energy-Carbon synergies and trade-offs in drinking water treatment plant upgrades - Yumeng Zhang; Zongqi Ding; Zewei Lin; Shoubin Chen; Shunjian Cheng; Kaiming Peng; Ru Guo; Xiangfeng Huang; Chen Cai; Jia Liu (Journal of Water Process Engineering, 2025)

Determination of pullout capacity for an inclined single-plate helical pile under combined loading in clay - Fei Liu; Po Cheng; Hongnan Lin; Jiangtao Yi; Yu Peng; Jun Hu; Ya-pei Chu (Marine Georesources & Geotechnology, 2025)

The effects of phospholipids (PL) addition in the high fat diet on growth performance, oxidative stress, lipid and protein metabolism, and muscle development in yellow catfish Pelteobagrus fulvidraco - Qing-Lin Li; Biao Wang; Hua Zheng; Li-Xiang Wu; Peng-Cheng Xu; Xiao-Ying Tan (Aquaculture, 2025)

Analytical solution for longitudinal equivalent bending stiffness of large-diameter shield tunnels with internal structures - Tao Chen; Huai-Na Wu; De-Sai Guo; Xin-Xin Yang; Hong-Zhan Cheng; Lin-Song Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2025)

Digital infrastructure construction and urban industrial chain resilience: Evidence from the “Broadband China” strategy - Yi Chen; Cailou Jiang; Lin Peng; Shuang Zhao; Cheng Chen (Sustainable Cities and Society, 2025)

Sesquiterpenoids from Inula britannica and their potential mechanism for immunomodulation - Hui-Lin Zhang; Na Wang; Xu-Liu Shi; Miao-Miao Wang; Qi-Meng Zhu; Jing Chang; Yan-Li Feng; Juan Zhang; Feng Qiu; Cheng-Peng Sun (Phytochemistry, 2025)

Detecting monogenic disorders in utero non-invasively based on fetal nucleated red blood cells highly-purified by multi-functional magnetic nanoparticles - Lin Cheng; Chun Feng; Ke Wu; Zixiang Wang; Wentao Zhu; Ting Geng; Naiqi Li; Jiawei Kang; Jie Duan; Jin Li; Yuqi Shao; Saisai Yang; et al. (Analytica Chimica Acta, 2025)

Versatile g-C3N4/AlOOH nanocomposites: Efficient photocatalyst for dye removal, algae inactivation, and glucose detection - Hsiu-Cheng Chen; Ting-Yu Lin; Hsin-Cheng Peng; Yu-Hsuan Lee; Ruey-Chi Wang (Chemosphere, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Application of 3-D inversion of AMT data in exploration of concealed nonmetallic deposits: A Case Study on the Huashitou Mountain fluorite deposit in Beishan metallogenic belt, China - Jianhui Hu; Liuyang Xu; Yaotian Yin; Xu Jia; Ping Qi; Zhan Liang; Peng Su; Cheng Liu; Weidong Tang; Long Chen; Yanzhou Wang; Lin Liu (Journal of Applied Geophysics, 2025)

Mechanical properties of a novel fiber-bridging interface for connecting FRP profile and concrete - Hongwei Lin; Haidong Qu; Peng Feng; Huixin Zeng; Guanzhi Cheng (Engineering Structures, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

Phosphomolybdic acid boosts polyunsaturated fatty acid and neutral lipid production in Phaeodactylum tricornutum - Kun-Tao Peng; Bing-Hong Xiong; Gao Cheng; Yuan-Hong Zhong; Lin Yu (Frontiers in Marine Science, 2025)
Phaeodactylum tricornutum is considered a potential lipid production platform due to its high growth rates and elevated natural neutral lipid and polyunsaturated fatty acid (PUFA) contents. Furthermore, microalgae are emerging as promising sources of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). In this study, phosphomolybdic acid (PMo 12 ), as a photocatalyst, can enhance the synthesis of neutral lipids and PUFAs by influencing the expression of lipid metabolism-related genes and photosynthesis in P. tricornutum. We also observed the contents of EPA and PUFA in engineered microalgae nearly doubled compared to the wild type, while neutral lipid content showed a significant increase of 69.7% in engineered microalgae. Notably, the growth rate of engineered microalgae remained comparable to that of the wild type. This work presents an effective approach to enhance the production of microalgal bioproducts, suggesting that photocatalysts such as PMo 12 could serve as viable alternatives to genetic engineering technology, facilitating the commercialization of microalgal biodiesel.

Dietary lecithin attenuates adverse effects of high fat diet on growth performance, lipid metabolism, endoplasmic reticulum stress and antioxidant capacity in the intestine of largemouth bass (Micropterus salmoides) - Hua Zheng; Biao Wang; Qing-Lin Li; Tao Zhao; Peng-Cheng Xu; Yu-Feng Song; Zhi Luo (Aquaculture, 2025)

Sex-specific associations between maternal exposure to metal mixtures and fetal growth trajectories: A prospective birth cohort study - Zhen-Hua Li; Cheng-Yang Hu; Si-Wei Dai; Hui-Ya Ma; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Xiu-Jun Zhang (Science of The Total Environment, 2025)

Triboelectric materials with UV protection, anti-bacterial activity, and green closed-loop recycling for medical monitoring - Jiandan Liang; Qiuxiang Yang; Ce Zhang; Wen Jiang; Shounian Cheng; Yang Tao; Lin Peng; Yu Han; Xia Cao; Zhong Lin Wang (Chemical Engineering Journal, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

Immobilizing lead in aqueous solution and loess soil using microbially induced carbonate/phosphate precipitation (MICP/MIPP) under harsh pH environments - Zhong-Fei Xue; Wen-Chieh Cheng; Lin Wang; Yi-Xin Xie; Peng Qin; Cong Shi (Journal of Hazardous Materials, 2024)

The mining of thermostable β-glucosidase for tea aroma enhancement under brewing conditions - Qi Lin; Cheng Peng; Kunpeng Yu; Yanling Lin; Yongquan Xu; Lijun Li; Hui Ni; Feng Chen (Food Chemistry, 2024)

Ultra-capacity and low-cost P3-type K0.5Mn0.96Fe0.04O2 cathode materials for K-ion batteries - Jun Cong; Shao-hua Luo; Yi-cheng Lin; Peng-yu Li; Li-xiong Qian; Sheng-xue Yan; Xin Liu; Xue-fei Lei (Chemical Engineering Journal, 2024)

Blocking endogenous phosphorus release in sediments by a hydrotalcite mixture synthesized with natural sepiolite and discarded cans - Fulong Cheng; Jie Pan; Changxin Zhao; Wei Li; Yuting Peng; Zuo Zhang; Yanjuan Lin; Guowen Chen (Applied Clay Science, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Insights on aggregation-algae consortium based removal of sulfamethoxazole: Unraveling removal effect, enhanced method and toxicological evaluation - Yongtao Cheng; Yuanyuan Wu; Chuanyue Peng; Yang Yang; Liang Xuan; Lin Wang; Yan Wang; An Xu; Ying Liu (Journal of Environmental Management, 2024)

Effects of physical sterilization on microbial safety, nutritional composition, and antioxidant activity of queen bee larva powder, a by-product of royal jelly production - Yu-Hsin Chen; Jer-An Lin; Chi-Chung Peng; Pei-Shou Hsu; Tzu-Hsien Wu; Yen-Hou Chen; Ming-Cheng Wu (Food Control, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

An analytical model of longitudinal joints in the segmental lining of shield tunnels with considering geometric nonlinearity - Dong-Lin Feng; Huai-Na Wu; Ren-Peng Chen; Si-Qi Yang; Hong-Zhan Cheng (Tunnelling and Underground Space Technology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

TaSRT2 recognizes a viral protein to activate host immunity by increasing histone acetylation - Kaili Zhong; Yaoyao Jiang; Haichao Hu; Bowen Yuan; Mila Wu; Aizhu Tu; Gecheng Xu; Linna Cai; Tingting Liu; Shiqi Gao; Linzhi Li; Qiansheng Liao; et al. (Science Bulletin, 2024)

Corrigendum to “Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L.” [Phytochem. Lett. 55 2023, 61–66] - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2024)

Conductive, biodegradable multi-array smart bandage for gesture recognition and motion detection - Wen Jiang; Yudong Wang; Qiuxiang Yang; Yang Tao; Lin Peng; Ce Zhang; Shounian Cheng; Jiandan Liang; Jinming Ma; Xia Cao (Chemical Engineering Journal, 2024)

High-molecular-weight dissolved organic matter enhanced phosphorus availability in paddy soils: Evidence from field and microcosm experiments - Hai-Bo Wang; Xi-Peng Liu; Bing-Jie Jin; Yu-Chen Shu; Cheng-Liang Sun; Yong-Guan Zhu; Xian-Yong Lin (Soil and Tillage Research, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

An effective preserving strategy for strawberries by constructing pectin/starch coatings reinforced with functionalized eggshell fillers - Hao Xu; Yihao Huang; Kuang He; Ziqiang Lin; David Julian McClements; Yao Hu; Hao Cheng; Xinwen Peng; Zhengyu Jin; Long Chen (Food Chemistry, 2024)

Fabrication of a label-free electrochemical immunosensor by functionalized nanofiber membrane for the ultrasensitive detection of quinalphos - Jian-cheng Hu; Peng Wen; Yu Wang; Jin-yi Yang; Zhi-li Xiao; Zhen-lin Xu; Yu-dong Shen; Hong Wang; Bruce D. Hammock (Food Control, 2024)

The relationship between landscape pattern and plant species diversity in east Dongting lake wetland based on different Eco-environment - Dongdong Zhang; Yang Lin; Wei Xiao; Deming Wang; Zihe Wang; Xingjian Jin; Tianzhuo Cheng; Jie Zhang; Peng Yi (Environmental Pollution, 2024)

Warming enhanced the interaction effects of fungi and fungivores and soil potassium mineralization in tropical forest - Feng Sun; Guanzhao Yan; Wei Lin; Wei He; Xianli Cheng; Yingwen Li; Akash Tariq; Jordi Sardans; Josep Penuelas; Jinchuang Wang; Mei Wang; Yuelin Li; et al. (CATENA, 2024)

Memristive switching in the surface of a charge–density–wave topological semimetal - Jianwen Ma; Xianghao Meng; Binhua Zhang; Yuxiang Wang; Yicheng Mou; Wenting Lin; Yannan Dai; Luqiu Chen; Haonan Wang; Haoqi Wu; Jiaming Gu; Jiayu Wang; et al. (Science Bulletin, 2024)

Characterization of the individual domains of the Bacillus thuringiensis Cry2Aa implicates Domain I as a possible binding site to Helicoverpa armigera - Meng Meng; Cheng Shen; Manman Lin; Jiafeng Jin; Wei Chen; Xiao Zhang; Chongxin Xu; Xiaodan Hu; Qing Zhu; Chengyu Chen; Yajing Xie; Ofentse Jacob Pooe; et al. (Journal of Invertebrate Pathology, 2024)

Cu-based bubble and ion sieve for ampere-level hydrogen evolution - Si-Wei Yan; Chuan-Qi Cheng; Fei-Fei Zhang; Ze-Yu Zhang; Kui Lin; Peng-Fei Yin; Rui Zhang; Jing Yang; Cun-Ku Dong; Jing Mao; Hui Liu; Xi-Wen Du (Chemical Engineering Journal, 2024)

UV aging may enhance adsorption capacity of Poly (butylene adipate-co-terephthalate) (PBAT) to heavy metals and toxicity to zebrafish - Xing Cheng; Yipeng Hou; Xubing Lin; Chudan Wang; Baozhen Shen; Shengchi Zhuo; Zhen Li; Licheng Peng; Zengjian Su (Aquatic Toxicology, 2024)

Regulation of gene expression in the secondary metabolic synthesis pathway of Lonicera japonica Flos by yeast polysaccharides - Xu-peng Gu; Lin-lin Yang; Da-ming Qi; Di Zhang; Tian-liang Liu; Cheng-ming Dong (Physiology and Molecular Biology of Plants, 2024)

National-scale 10 m annual maize maps for China and the contiguous United States using a robust index from Sentinel-2 time series - Yingze Huang; Bingwen Qiu; Peng Yang; Wenbin Wu; Xuehong Chen; Xiaolin Zhu; Shuai Xu; Laigang Wang; Zhanjie Dong; Jianyang Zhang; Joe Berry; Zhenghong Tang; et al. (Computers and Electronics in Agriculture, 2024)

Recent progress in the hydrophobic modification of starch-based films - Ziqiang Lin; Hao Cheng; Kuang He; David Julian McClements; Zhengyu Jin; Zhenlin Xu; Man Meng; Xinwen Peng; Long Chen (Food Hydrocolloids, 2024)

Novel chitosan-modified biochar prepared from a Chinese herb residue for multiple heavy metals removal: Characterization, performance and mechanism - Chengjiu Wang; Jixu Qiao; Jiandan Yuan; Zhentao Tang; Tianzhe Chu; Ruifeng Lin; Hongting Wen; Chuan Zheng; Hulan Chen; Haijiao Xie; Cheng Peng; Yuzhu Tan (Bioresource Technology, 2024)

Studies on regional ozone formation sensitivities and transport with higher spatiotemporal resolutions in a stereoscopic dimension: GEMS and vertical observations - Haochen Peng; Chengzhi Xing; Yikai Li; Chengxin Zhang; Jinan Lin; Jingkai Xue; Xiaohan Wang; Yuhang Song; Xinhan Niu; Cheng Liu (Atmospheric Research, 2024)

Correction to: P2 purinergic receptors regulate the progression of colorectal cancer - Wen‑jun Zhang; Li‑peng Zhang; Si‑jian Lin; Cheng‑yi Wang; Yi-guan Le (Purinergic Signalling, 2024)

An observational prospective study based on a large cohort of HIV-negative neurosyphilis patients with particular reference to the Jarisch-Herxheimer reaction - Rui-Rui Peng; Juan Wu; Wei Zhao; Lin Zhu; Zhifang Guan; Xin Gu; Mei Shi; Junjun Yu; Yanchun Cheng; Pingyu Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The purpose of this study is to outline a complete picture of Jarisch-Herxheimer reaction (JHR) in the central nervous system among HIV-negative neurosyphilis patients. Methods A prospective study cohort of 772 cases with almost all stages of neurosyphilis depicted the features of JHR including occurrence rate, risk profiles, clinical manifestations, medical management and prognosis. Results The total occurrence rate of JHR was 9.3% (95% CI, 7.3-11.4%), including 4.1% (95% CI, 2.7-5.6%) with severe JHR. The reaction started 5 h after treatment initiation, peaked after 8 h, and subsided after 18 h. Patients with severe JHR experienced a longer recovery time (26 h). Patients with general paresis (OR = 6.825), ocular syphilis (OR = 3.974), pleocytosis (OR = 2.426), or a high CSF-VDRL titre (per log 2 titre increase, OR = 2.235) were more likely to experience JHR. Patients with general paresis had an 11.759-fold increased risk of severe JHR. Worsening symptoms included cognitive impairment, mania, nonsense speech, and dysphoria, while symptoms of hallucination, urination disorder, seizures, myoclonus, or aphasia appeared as new-onset symptoms. Neurosyphilis treatment did not need to be interrupted in most patients with JHR and could be reinstated in patients with seizures under supportive medication when JHR subsided. Conclusion Severe JHR displayed a 4.1% occurrence rate and clinicians should pay particular attention to patients at a higher risk of JHR. The neurosyphilis treatment regime can be restarted under intensive observation for patients with severe JHR and, if necessary, supportive medication should be initiated and continued until the end of therapy.

Effectiveness of a novel compound microbial agent for water quality and the gut microbiota of Micropterus salmoides - Qian Li; Li-Hui Sun; Bi-Cheng Yang; Jian-Hu Jiang; Jian-Ming Chen; Gang Zheng; Ling-Mei Gao; Jun Peng; Jian-Lin Guo (Frontiers in Marine Science, 2024)
The cultivation of largemouth bass ( Micropterus salmoides ), a species of significant economic value in aquaculture, has experienced notable growth recently. However, the deterioration of water quality seriously affects the metabolic responses of M. salmoides . While compound microbial agent (CMA) is widely utilized for ecological rehabilitation and water filtration, its application in M. salmoides has not been reported. Here, based on physio-biochemical tests and 16S rRNA sequencing, we investigated the effects of CMA (yeast, Bacillus subtilis , and lactic acid bacteria) on the water quality within the recirculating aquaculture system, along with physiological indices and gut microbiota of M. salmoides . Compared to the control and single microbial agent (yeast), CMA treatment improved the water quality by improving the dissolved oxygen and delaying the increase of pH, total nitrogen, total phosphorus, ammonia nitrogen, and nitrite. The 16s rRNA gene sequencing revealed that the water treated with CMA exhibited elevated levels of chao1, Shannon, Pd, and a larger population of dominant bacterial. Besides, higher values of ACE, chao1, Shannon, and OTU level, and lower Simpson index were found in CMA treated M. salmoides samples, suggesting that CMA treatment enhanced the species richness and diversity of gut microbiota of M. salmoides . Furthermore, CMA treatment hindered the generation and proliferation of harmful bacteria, such as the Mycoplasma mobile 163K species and the Erysipelotrichaceae family, which was associated with enhanced antioxidant enzymatic activity and decreased MDA level in both the serum and liver. These findings shed light on the essential roles of CMA in M. salmoides culturing and introduce an innovative approach to enhance the aquatic environment.

Fully automated learning and predict price of aquatic products in Taiwan wholesale markets using multiple machine learning and deep learning methods - Yi-Ting Lai; Yan-Tsung Peng; Wei-Cheng Lien; Yun-Chiao Cheng; Yi-Ting Lin; Chen-Jie Liao; Yu-Shao Chiu (Aquaculture, 2024)

Improved hourly estimate of aerosol optical thickness over Asian land by fusing geostationary satellites Fengyun-4B and Himawari-9 - Yueming Cheng; Tie Dai; Daisuke Goto; Lin Chen; Yidan Si; Hiroshi Murakami; Mayumi Yoshida; Peng Zhang; Junji Cao; Teruyuki Nakajima; Guangyu Shi (Science of The Total Environment, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Selective influence of the Arctic Oscillation on the Indian Ocean Dipole and El Niño-Southern Oscillation - Xin Cheng; Shangfeng Chen; Wen Chen; Renguang Wu; Ruowen Yang; Peng Hu; Lin Chen; Hasi Aru (Climate Dynamics, 2024)

Novel CRISPR/SpRY system for rapid detection of CRISPR/Cas-mediated gene editing in rice - Zhixun Su; Xiaofu Wang; Xiaoyun Chen; Lin Ding; Xiaoqun Zeng; Junfeng Xu; Cheng Peng (Analytica Chimica Acta, 2024)

Arsenic effectively improves the degradation of fluorene by Rhodococcus sp. 2021 under the combined pollution of arsenic and fluorene - Hong-Peng Shi; Ying-Hao Zhao; Mei-Lin Zheng; Cheng-Yan Gong; Lei Yan; Ying Liu; Yong-Ming Luo; Zhi-Pei Liu (Chemosphere, 2024)

Identification and functional analysis of insulin-like 3 during gonad development in the hermaphroditic orange-spotted grouper, Epinephelus coioides - Jin Zhang; Jing Wang; Wenrui Zhang; Jiaqi Lin; Jiayu Yang; Junyao Peng; Shimin Peng; Shuisheng Li; Yong Zhang; Cheng Peng (Aquaculture, 2024)

Insight into the interaction mechanism between mulberry polyphenols and β-lactoglobulin - Qi Yuan; Lin He; Xuping Wang; Huaigu Yang; Fan Zhu; Xiaoxia Peng; Jingrong Cheng; Yaosheng Lin; Daobang Tang; Xueming Liu (Food Hydrocolloids, 2024)

Effects of polypropylene microplastics on carbon dioxide dynamics in intertidal mangrove sediments - Xubing Lin; Shuying Lin; Licheng Peng; Miao Chen; Xing Cheng; Shiyu Xie; Ruiqi Bao; Yuanyuan Su; Tariq Mehmood (Environmental Pollution, 2024)

Answer to Comment on: ‘Bibliometrics of the nexus between food security and carbon emissions: Hotspots and trends’, By Kong Xuesong et al. DOI: https://doi.org/10.1007/s11356-022-23970-1. Environ. Sci. Pollut. Res. 30 (2023) 25981-25998 - Peng Cheng; Houtian Tang; Feifei Lin; Xuesong Kong (Environmental Science and Pollution Research, 2024)

Unequal transfer and its policy implications of carbon emissions and economic benefits embodied among Central Plains urban agglomeration - Shuan Peng; Min Chen; Zefeng Qi; Nihed Benani; Tao Wang; Xuefang Wu; Xi Cheng; Jian Lin Chen; Guozhu Mao; Pingjian Yang (Urban Climate, 2024)

Main controlling factors evolution on high-quality source rocks development in the Shanan Sag, Bohaibay Basin, NE China: Implication from structure, depositional environment, and organic matter - Jinjun Xu; Juncai Jiang; Deying Wang; Peng Xu; Feilong Wang; Huiyong Li; Xiangang Cheng; Qilong Wu; Fuqi Cheng; Lamei Lin; Yinbo Xu (Journal of Asian Earth Sciences, 2024)

Analytical modeling for the behavior of concrete-cored cement mixing (CCM) pile composite foundation under embankment - Jian-lin Yu; Jin-peng Chen; Jia-jin Zhou; Jia-cheng Xu; Xiao-nan Gong (Computers and Geotechnics, 2024)

PM2.5-bound heavy metals in a typical industrial city of Changzhi in North China: Pollution sources and health risk assessment - Hao Chen; Yulong Yan; Dongmei Hu; Lin Peng; Cheng Wang (Atmospheric Environment, 2024)

Genome-wide identification of heat shock protein gene family and their responses to pathogen challenge in Trachinotus ovatus - Yi-Yao Sun; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Ke-Cheng Zhu; Lin Xian; Peng-Hai Zhao; Hui-Yuan Yang; Dian-Chang Zhang (Fish & Shellfish Immunology, 2024)

Foraging flight-based health indicators for honey bee colonies using automatic monitoring systems - Joe-Air Jiang; Jen-Cheng Wang; Chien-Peng Huang; Mu-Hwa Lee; An-Chi Liu; Hung-Jen Lin; Chien-Hao Wang; Cheng-Ying Chou; En-Cheng Yang (Computers and Electronics in Agriculture, 2024)

Effect of Streptomyces JD211 application on soil physicochemical properties and N2O emission characteristics of rice rhizosphere - Hailong Peng; Tianyu Xu; Lixin Wang; Jiaqing Yu; Xin Chen; Xin Cheng; Hanguang Li; Lin Huang; Lei Wei; Saijin Wei (Science of The Total Environment, 2024)

Gaseous signaling molecule H2S as a multitasking signal molecule in ROS metabolism of Oryza sativa under thiocyanate (SCN−) pollution - Yu-Xi Feng; Peng Tian; Yu-Juan Lin; Dan-Yang Cao; Cheng-Zhi Li; Abid Ullah (Environmental Pollution, 2024)

Response of distributions and emissions of summer biogenic sulfur in the Pacific Arctic to enhanced Pacific Water inflow - Cheng‐Xuan Li; Bao‐Dong Wang; Kan Chen; Gui‐Peng Yang; Jian‐Fang Chen; Li‐Na Lin; Zi‐Cheng Wang (Limnology and Oceanography, 2024)
The inflow of warm and nutrient‐rich Pacific Water (PW) through the Bering Strait into the Arctic Ocean is likely to have far‐reaching consequences for the ecosystem and biogenic sulfur cycle in the Earth's sensitive subarctic–arctic region of the Pacific sector, even impacting climate change under global warming scenarios. We performed a detailed biogeochemical study of summer biogenic sulfur cycling from cold (2012) to warm (2014) years in the Bering Strait and the Chukchi Sea, so as to highlight the importance of enhanced Pacific inflow in driving dimethylsulfide (DMS) variability. In the Bering Strait, the enhanced Pacific inflow led to the vertical expansion of the eastern high‐DMS regions due to the vertical extension of Alaska Coastal Water, and the horizontal expansion of the western surface high‐DMS regions due to the westward intrusion of Bering Shelf Water. The enhanced extension of PW potentially stimulated seawater warming, the northward retreat of the ice edge, and the enlargement of sea ice‐free areas in the Chukchi Sea. The northern ice melting zone at 71°N with a bloom of phytoplankton was an area of locally high dimethylsulfoniopropionate concentrations and slow DMS consumption in 2012. A hotspot for dimethylated sulfur compound concentrations and DMS sea–air flux occurred in the convergence region near 67.7°N during 2014, due to enhanced mixing caused by increased Bering Sea Water. Owing to the increased advection of PW during 2012–2014, surface DMS and its emission to the atmosphere increased sharply by threefold in the Chukchi Sea.

Hierarchical Y zeolite with accessible intracrystalline mesopores and enhanced hydrocracking performances via sequential multi-carboxyl acid and fluoroborate post-treatments - Lin-Jiao Wei; Peng Peng; Ke Qiao; Guang-Nan Cheng; Ubong Jerome Etim; Zi-Feng Yan (Fuel, 2023)

Applying the first microcapsule-based self-healing microbial-induced calcium carbonate materials to prevent the migration of Pb ions - Zhong-Fei Xue; Wen-Chieh Cheng; Lin Wang; Peng Qin; Yi-Xin Xie; Wenle Hu (Environmental Research, 2023)

Joint effects of prenatal exposure to air pollution and pregnancy-related anxiety on birth weight: A prospective birth cohort study in Ma’anshan, China - Zhen-Hua Li; Yi-Cheng Mao; Yang Li; Sun Zhang; Hui-Yu Hu; Zhe-Ye Liu; Xue-Jie Liu; Jia-Wen Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Research, 2023)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Joint full waveform inversion of multiple instantaneous attributes - Kai Zhang; Yi-peng Xu; Fei Xie; Cheng-hong Zhu; Zhen-chun Li; Zi-Lin He (Applied Geophysics, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

An accurate and efficient HOS-meshfree CFD coupling method for simulating strong nonlinear wave–body interactions - Chun-Mei Xie; Jun-Cheng Yang; Peng-Nan Sun; Hong-Guan Lyu; Jun Yu; Yong-Lin Ye (Ocean Engineering, 2023)

Genome architecture and tetrasomic inheritance of autotetraploid potato - Zhigui Bao; Canhui Li; Guangcun Li; Pei Wang; Zhen Peng; Lin Cheng; Hongbo Li; Zhiyang Zhang; Yuying Li; Wu Huang; Mingwang Ye; Daofeng Dong; et al. (Molecular Plant, 2023)

Where does floating Sargassum in the East China Sea come from? - Lin Qi; Peng Cheng; Menghua Wang; Chuanmin Hu; Yuyuan Xie; Keyu Mao (Harmful Algae, 2023)

Selective hydrocracking of poly-aromatics to mono-aromatics in a catalyst grading system of NiMo/Al2O3-HY and NiMo/Beta - Lin Qi; Chong Peng; Zhenmin Cheng; Zhiming Zhou (Fuel, 2023)

Effects of mulberry pomace polysaccharide addition before fermentation on quality characteristics of yogurt - Huaxin Du; Xuping Wang; Huaigu Yang; Fan Zhu; Jingrong Cheng; Xiaoxia Peng; Yaosheng Lin; Xueming Liu (Food Control, 2023)

Effect of the inoculation of Phanerochaete chrysosporium on nitrogen migration and organic matter conversion during electrolytic manganese residue composting - Xiangyu Peng; Ming Yan; Qingqing Xie; Lan Gao; Xiaojuan Pu; Yukui Fu; Hanwen Liu; Min Cheng; Piao Xu; Danlian Huang; Lin Tang (Bioresource Technology, 2023)

Seasonal Disparities of Human Health Risk and Particle-Bound Metal Characteristics Associated with Atmospheric Particles in a Fishery Harbor - Cheng-Yun Tsai; Yen-Ping Peng; Chia-Hua Lin; Ku-Fan Chen; Chia-Hsiang Lai; Pin-Hao Qiu (Archives of Environmental Contamination and Toxicology, 2023)

Pectin-nanolignin composite films with water resistance, UV resistance, and antibacterial activity - Shikai Zhang; Xinxin Cheng; Quanbin Fu; Yijing Li; Peng Wu; Yiheng Qiao; Jianfeng Yan; Lin Si; Geoffrey I.N. Waterhouse; Houshen Li; Shiyun Ai (Food Hydrocolloids, 2023)

The effects of prenatal PM2.5 oxidative potential exposure on feto-placental vascular resistance and fetal weight: A repeated-measures study - Weiwei Lin; Yuming Lai; Shuling Zhuang; Qiannan Wei; Hedi Zhang; Qiansheng Hu; Peng Cheng; Manman Zhang; Yuhong Zhai; Qingqing Wang; Zhenyan Han; Hongying Hou (Environmental Research, 2023)

Bond behavior of FRP-concrete wet-bonding interface under lateral confinement - Hongwei Lin; Huixin Zeng; Peng Feng; Cheng Jiang; Yuqing Zhang (Engineering Structures, 2023)

Earthworms enhance the inhibition efficiency of 3,4-dimethylpyrazole phosphate on soil nitrification by altering soil AOB communities and gut denitrifier communities - Bing-Jie Jin; Xi-Peng Liu; Miao Zhang; Yan Hu; Cheng-Liang Sun; Gang Li; Yong-Guan Zhu; Xian-Yong Lin (Biology and Fertility of Soils, 2023)

Evidence for the Late Pliocene Aridification in the Eastern Tarim Basin, Northwest China - Hua Zhang; Feng-Lin Lü; Cheng-Lin Liu; Peng-Cheng Jiao; Hui-Jing Yin; Hui Yan; Bao-Cheng Ma; Liang-Liang Zhao; Hong-Chao Liu (Journal of Earth Science, 2023)

Spatiotemporal Interaction Between Rural Settlements and Cultivated Land in Karst Mountainous Area, China - Feifei Lin; Peng Cheng; Xuesong Kong (Chinese Geographical Science, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Chain hybridization‐based CRISPR‐lateral flow assay enables accurate gene visual detection - Meng Cheng; Caiwei Tan; Bo Xiang; Weihong Lin; Bolin Cheng; Xuechun Peng; Yihao Yang; Yongping Lin (Analytica Chimica Acta, 2023)

DRL-based target interception strategy design for an underactuated USV without obstacle collision - Chenming Zhang; Peng Cheng; Bin Lin; Weidong Zhang; Wei Xie (Ocean Engineering, 2023)

Applicability of carbonate clumped isotope thermometry in the Tuchang-Jentse geothermal field - Yi-Chia Lu; Sheng-Rong Song; Ling-Wen Liu; Tsung-Ren Peng; Bill Bing-Cheng Chen; Remy Kai-Cheng Tu; Li-Hung Lin; Pei-Ling Wang (Geothermics, 2023)

A fractional-order two-surface plasticity model for over-consolidated clays and its application to deep gallery excavation - Wei Cheng; Ren-Peng Chen; Zhen-Yu Yin; Han-Lin Wang; Fan-Yan Meng (Computers and Geotechnics, 2023)

Phosphorus amendment alters soil arbuscular mycorrhizal fungal functional guild compositions in a subtropical forest - Quan-Cheng Wang; Sheng-Sheng Jin; Shanshan Liu; Ge Song; Chunjian Duan; Peng-Peng Lü; Pulak Maitra; Lin Xie; Yongxin Lin; Hang-Wei Hu; Ji-Zheng He; Yong Zheng (Journal of Soils and Sediments, 2023)

Hyperspectral imaging technique supports dynamic emission inventory of coal-fired power plants in China - Jinan Lin; Chengzhi Xing; Cheng Liu; Wei Tan; Wei Wang; Peng Wu; Chuan Lu; Qihua Li; Ting Liu (Science Bulletin, 2023)

Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L. - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2023)

Artificial intelligence and visual analytics in geographical space and cyberspace: Research opportunities and challenges - Min Chen; Christophe Claramunt; Arzu Çöltekin; Xintao Liu; Peng Peng; Anthony C. Robinson; Dajiang Wang; Josef Strobl; John P. Wilson; Michael Batty; Mei-Po Kwan; Maryam Lotfian; et al. (Earth-Science Reviews, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Tumor microenvironment-responsive nanosystem achieves reactive oxygen species self-cycling after photothermal induction to enhance efficacy of antitumor therapy - Yuting Peng; Lianghao Cheng; Chunyi Luo; Fuquan Xiong; Zhiping Wu; Lin Zhang; Peng Zhan; Lishu Shao; Weihua Luo (Chemical Engineering Journal, 2023)

MicroRNA-650 Regulates the Pathogenesis of Alzheimer’s Disease Through Targeting Cyclin-Dependent Kinase 5 - Li Lin; Xiaodong Liu; Xuejun Cheng; Yujing Li; Marla Gearing; Allan Levey; Xiaoli Huang; Ying Li; Peng Jin; Xuekun Li (Molecular Neurobiology, 2023)
Alzheimer’s disease (AD) pathogenesis feature progressive neurodegeneration, amyloid-β plaque formation, and neurofibrillary tangles. Ample evidence has indicated the involvement of epigenetic pathways in AD pathogenesis. Here, we show that the expression of microRNA 650 (miR-650) is altered in brains from AD patients. Furthermore, we found that the processing of primary miR-650 to mature miR-650 is misregulated. Bioinformatic analysis predicted that miR-650 targets the expression of three AD-associated components: Apolipoprotein E (APOE), Presenilin 1 (PSEN1), and Cyclin-Dependent Kinase 5 (CDK5), and we have experimentally confirmed that miR-650 is able to significantly reduce the expression of APOE, PSEN1, and CDK5 in vitro. Importantly, the overexpression of miR-650 was further shown to significantly alter the CDK5 level and ameliorate AD pathologies in APP-PSEN1 transgenic mice. Overall, our results indicate that miR-650 influences AD pathogenesis through regulation of CDK5.

Full-length transcriptome sequence and SSR marker development for genetic diversity research in yellowfin seabream Acanthopagrus latus - Jin Zhang; Jinmei Liu; Chong Han; Cheng Peng; Yong Li; Junhong Xia; Yong Zhang; Shuisheng Li; Haoran Lin (Journal of Oceanology and Limnology, 2023)

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Two Novel Species of Mesophoma gen. nov. from China - Ai-Ling Yang; Lin Chen; Lu Cheng; Jin-Peng Li; Zhao-Ying Zeng; Han-Bo Zhang (Current Microbiology, 2023)

Cytotoxic steroidal glycosides from the rhizomes of Paris polyphylla var. yunnanensis - Yang Liu; Mei-You Liu; Lin-Lin Bi; Yun-Yuan Tian; Peng-Cheng Qiu; Xiao-Ying Qian; Min-Chang Wang; Hai-Feng Tang; Yun-Yang Lu; Bang-Le Zhang (Phytochemistry, 2023)

Diverse alkaloids from the aerial parts of Aconitum carmichaelii and antiproliferative activity of costemline via inhibiting SIRT1/ROCK1/P-STAT3 pathways - Yin-Lin Zhou; Duan-Na Zhang; Ji-Xu Qiao; Jing Wu; Yong-Ming Yan; Zhi-Xing Cao; Cheng Peng; Yu-Zhu Tan (Phytochemistry, 2023)

Miocene rapid strike-slip faulting along the Altyn Tagh Fault, North Tibet: Insight from sedimentology records in the Tula and Qaidam basins - Zhongcheng Zeng; Lin Wang; Peng Wang; Zenglin Hong; Feng Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Continuous rotating bending NiTi sheets for elastocaloric cooling: Model and experiments - Siyuan Cheng; Yinan Xiao; Xueshi Li; Hongyang Lin; Peng Hua; Liyuan Sheng (International Journal of Refrigeration, 2023)

DOK7 Promotes NMJ Regeneration After Nerve Injury - Ethan D. Kosco; Hongyang Jing; Peng Chen; Wen-Cheng Xiong; Ivy S. Samuels; Lin Mei (Molecular Neurobiology, 2023)

Stem cell-derived exosomes for chronic wound repair - Peng Mi; Jia-Lin Liu; Bao-Ping Qi; Ben-Mei Wei; Cheng-Zhi Xu; Lian Zhu (Cell and Tissue Research, 2023)

2000 years of lake-level fluctuations and human adaptation around China's largest freshwater lake - Huanye Wang; Weiguo Liu; Qin Leng; Lin Yang; Hui Zhao; Jun Yang; Yuwei Chen; Shangbin Xiao; Yunning Cao; Jing Hu; Xiaoke Qiang; Peng Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

A new catalyst CHCP-Fe2O3 for enhanced removal of tetracycline through the Fenton-like process: Economical synthesis, catalytic performance, and practicability - Jiao He; Baoyou Pei; Chenglong Deng; Dongha Huang; Bihong Lv; Cheng Peng; Genggeng Luo; JinQing Lin (Journal of Water Process Engineering, 2023)

A conductive hydrogel based on nature polymer agar with self-healing ability and stretchability for flexible sensors - Zhen Nie; Kelin Peng; Lizhi Lin; Jueying Yang; Zhekun Cheng; Qiang Gan; Yu Chen; Changgen Feng (Chemical Engineering Journal, 2023)

Patterns of organic carbon and nitrogen stocks in soil particle-size fractions along an aridity gradient in Northern China’s deserts - Yan-gui Su; Gang Huang; Si-nuo Lin; Zheng-yi Huang; Guo-peng Wu; Hao Cheng (CATENA, 2023)

High contribution of vehicular exhaust and coal combustion to PM2.5-bound Pb pollution in an industrial city in North China: An insight from isotope - Hao Chen; Yulong Yan; Dongmei Hu; Lin Peng; Cheng Wang (Atmospheric Environment, 2023)

Intercropping with maize (Zea mays L.) enhanced the suppression of pepper (Capsicum annuum L.) Phytophthora blight by arbuscular mycorrhizal fungi - Junli Hu; Shaowei Hou; Peng Cai; Minghui Li; Zhang Cheng; Fuyong Wu; Xiangui Lin (Journal of Soils and Sediments, 2023)

Combined effects of prenatal phthalate exposure on cardiometabolic risk score among 4- to 7-year-old children: MABC study - Hui Gao; Meng-long Geng; Juan Tong; Bao-lin Wang; Kun Huang; Yi Zhang; Hong Gan; Bei-bei Zhu; Peng Ding; Qu-nan Wang; Jian-qing Wang; Cheng Zhang; et al. (Chemosphere, 2023)

Surface characteristics of polystyrene microplastics mainly determine their coagulation performances - Jingjing Yao; Zhaoxia Peng; Weifeng Chen; Qingyuan Lin; Mengsi Cheng; Haipu Li; Ying Yang; Hui Ying Yang (Marine Pollution Bulletin, 2023)

Catalytic transfer hydrogenation of biomass-derived furfural into furfuryl alcohol over zirconium doped nanofiber - Wansi Lin; Yuan Cheng; Huai Liu; Junhua Zhang; Lincai Peng (Fuel, 2023)

Bibliometrics of the nexus between food security and carbon emissions: hotspots and trends - Peng Cheng; Houtian Tang; Feifei Lin; Xuesong Kong (Environmental Science and Pollution Research, 2022)

Horizontal and vertical heterogeneity of sediment microbial community in Site F cold seep, the South China Sea - Xinyi Zhai; Xiaochong Shi; Haojin Cheng; Peng Yao; Bin Zhao; Lin Chen; Jiwen Liu; Lei Cao; Minxiao Wang; Lulu Fu; Xiao-Hua Zhang; Min Yu (Frontiers in Marine Science, 2022)
Site F is the most vigorous cold seep known on the continental slope of the northern South China Sea. Up to now, the microbial community structures in sediments of Site F based on the high-throughput sequencing of the 16S rRNA genes have been studied extensively. However, few studies investigated the microbial community structures at fine vertical scales of Site F and control stations outside Site F. In this study, a comprehensive investigation of microbial communities in sediments of Site F along the depths varying from 0 to 24 cm below sea floor (cmbsf) of four sampling sites—SRS (Southern Reduced Sediment), NRS (Northern Reduced Sediment), Control 1 (close to Site F), and Control 2 (far from Site F)—was carried out. The high relative abundances of anaerobic methanotrophic archaea (ANME), Desulfobacterota [sulfate-reducing bacteria (SRB)], and Campylobacteria [sulfur-oxidizing bacteria (SOB)] in SRS and NRS indicated that these two sites were newborn cold seep sites compared with non-seep sites, Control 1, and Control 2. A positive correlation between ANME-1b, ANME-2, and SEEP-SRB and an enrichment of Sulfurovum and Methlomonadaceae were found in the surface sediments of both SRS and NRS, indicating that the processes of anaerobic oxidation of methane (AOM), sulfur oxidation, and sulfate reduction might occur in seep sites. SRS was enriched with ANME-1b and SEEP-SRB2 with a proposed sulfate-methane transition zone (SMTZ) approximately located at 8 cmbsf. The high abundance of ANME in SRS may due to the high concentration of methane. NRS was enriched with ANME-2, Desulfatiglans , Sulfurovum , and Methanosarcinaceae with a proposed SMTZ at about 10 cmbsf. According to the analyses of microbial community structure and environmental factors, NRS could be described as a notable cold seep reduced sediment site with low sulfate and high H 2 S that nourished abundant SEEP-SRB1, ANME-2, Methanosarcinales , and Sulfurovum , which showed similar distribution pattern. Our study expands the current knowledge on the differences of microbial communities in cold seep sites and non-seep sites and sheds light on the horizontal and vertical heterogeneity of sediment microbial community in Site F.

Isolation and identification of two new sargentodoxosides from Sargentodoxa cuneata and their agonistic effects against FXR - Wen Zhang; Cheng-Peng Sun; Yu-Lin Peng; Wen-Yu Zhao; Zheng-Yue Wang; Jing Ning; Xia Lv; Zhen-Long Yu; Shuang Zhou; Wei Peng; Bang-Jiang Fang; Xiao-Chi Ma (Natural Product Research, 2022)

Spatiotemporal characteristics and influencing factors of urban resilience efficiency in the Yangtze River Economic Belt, China - Yingzi Lin; Chong Peng; Jianfeng Shu; Wei Zhai; Jianquan Cheng (Environmental Science and Pollution Research, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Myd88 knockdown with RNA interference induces in vitro immune hyporesponsiveness in dendritic cells from rhesus monkeys - Qiuhong Wang; Dongyun Cun; Desong Xu; Liang Lin; Jian Jiao; Li Zhang; Cheng Xi; Wei Li; Peng Chen; Mingdao Hu (Immunogenetics, 2022)

Characteristics of the chemical composition and source apportionment of PM2.5 for a one-year period in Wuhan, China - Xiaoyu Zhang; Guixiang Ji; Xiaowu Peng; Lingya Kong; Xin Zhao; Rongrong Ying; Wenjun Yin; Tian Xu; Juan Cheng; Lin Wang (Journal of Atmospheric Chemistry, 2022)

Secoiridoid glycosides from the fruits of Cornus officinalis - Xin Wang; Xiang-Jian Zhong; Na Zhou; Lin-Lin Ji; Jin-Jie Li; Ning Cai; Qing-Bo Wang; Peng-Cheng Lin; Xiao-Ya Shang (Natural Product Research, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Distribution characteristics of per- and polyfluoroalkyl substances (PFASs) in human urines of acrylic fiber plant and chemical plant - Lin Peng; Wang Xu; Qinghuai Zeng; Yao Cheng; Yingjie Zhang; Ying Guo; Da Chen; Chao Jiang; Fei Wang (Environmental Science and Pollution Research, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Development of a dual-labeled, hydrolysis probe-based, real-time quantitative PCR assay for detection of both genotypes of duck circovirus-1 (DuCV-1) and DuCV-2 - Lin Zhang; Wenming Jiang; Fuyou Zhang; Yang Li; Jinping Li; Shaobo Liang; Xiaohui Yu; Cheng Peng; Shuo Liu; Jingjing Wang; Shuhong Sun; Hualei Liu (Virus Genes, 2021)

Applying Artificial Intelligence (AI) Techniques to Implement a Practical Smart Cage Aquaculture Management System - Chung-Cheng Chang; Jung-Hua Wang; Jenq-Lang Wu; Yi-Zeng Hsieh; Tzong-Dar Wu; Shyi-Chy Cheng; Chin-Chun Chang; Jih-Gau Juang; Chyng-Hwa Liou; Te-Hua Hsu; Yii-Shing Huang; Cheng-Ting Huang; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose This paper presents our team’s results to establish an AIoT smart cage culture management system. Methods According to the built system, the farmed field information is transmitted to the data platform of Ocean Cloud, and all collected data and analysis results can be applied to the cage culture field after the bigdata analysis. Results This management system successfully integrates AI and IoT technologies and is applied in cage culture. Using underwater biological analysis images and AI feeding as examples, this paper explains how the system integrates AI and IoT into a feasible framework that can constantly acquire information about the health status of fish, survival rate of fish, as well as the feed residuals. Conclusion The results of our research enable the aquaculture operators or owners to efficiently reduce the feed residual, monitor the growth of fish, and increase fish survival rate, thereby increasing the feed conversion rate.

Acute associations between air pollution on premature rupture of membranes in Hefei, China - Chao Zhang; Sha Li; Gan-lan Guo; Jing-wen Hao; Peng Cheng; Li-lin Xiong; Shu-ting Chen; Ji-yu Cao; Yu-wen Guo; Jia-hu Hao (Environmental Geochemistry and Health, 2021)

The major photoprotective role of anthocyanins in leaves of Arabidopsis thaliana under long-term high light treatment: antioxidant or light attenuator? - Xiao-Ting Zheng; Zheng-Chao Yu; Jun-Wei Tang; Min-Ling Cai; Yi-Lin Chen; Cheng-Wei Yang; Wah Soon Chow; Chang-Lian Peng (Photosynthesis Research, 2021)

Natural constituents from food sources as therapeutic agents for obesity and metabolic diseases targeting adipose tissue inflammation - Dan Li; Tian Zhang; Jinjian Lu; Cheng Peng; Ligen Lin (Critical Reviews in Food Science and Nutrition, 2021)

Identification of potential sex-related genes in Siniperca chuatsi - Qiaoying Zhu; Chong Han; Cheng Peng; Xingni Zhou; Chongwei Wang; Linqiang Han; Shuisheng Li; Guifeng Li; Haoran Lin; Yong Zhang (Journal of Oceanology and Limnology, 2021)

PtP38 May Increase the Immune Ability of Portunus trituberculatus Stimulated by LPS Imitating a Gram-Negative Bacterial Infection - Cheng-Peng Lu; Chao-Guang Wei; Jun-Quan Zhu; Dao-Jun Tang; Chun-Lin Wang; Cong-Cong Hou (Frontiers in Marine Science, 2021)
The P38 mitogen-activated protein kinase (MAPK) signal transduction pathway is widespread in organisms and plays important roles in immune activities. The infection mechanism of environmental gram-negative bacteria on crustaceans is an important scientific problem. In this study, the cDNA full-length sequence of Portunus trituberculatus P38 (PtP38) was cloned and its structure was analyzed by bioinformatics methods. To study the function of the PtP38 gene after a Gram-negative bacterial infection, we injected P. trituberculatus with LPS to activate the immune response instead of directly infecting with Gram-negative bacteria. With LPS stimulation, the expression of the PtP38 gene in different tissues increased significantly. At the same time, the expression of immune-related genes (ALF and crustin) in the hepatopancreas, activities of antioxidant enzymes [superoxide dismutase (SOD), catalase (CAT), and inducible nitric oxide synthase (iNOS) enzymes], and expression of apoptosis-related genes (caspase2 and caspase3) were increased significantly. To further conform the function of PtP38 in the immune response, we injected P. trituberculatus with P38 inhibitor and subsequently injected with LPS. The results showed that the expression of immune-related genes was inhibited, the activity of antioxidant enzymes was decreased, and the expression of apoptosis-related genes were inhibited. Thus, we speculated that PtP38 may increase the immune ability by improving the expression of antimicrobial peptides, increasing the activity of oxidative stress-related enzymes, and promoting cell apoptosis in infected P. trituberculatus . This study also laid the foundation for further study of the P38 MAPK signaling pathway and immune mechanism of P. trituberculatus .

Cabbage defense response provoked by Trichoderma Th-LAAO - Chia-Min Liu; Shu-Ying Liu; Chuan-Kai Liao; Chaur-Tsuen Lo; Kuo-Chih Lin; Kou-Cheng Peng (Archives of Microbiology, 2021)

Physical interactions facilitate sex change in the protogynous orange‐spotted grouper, Epinephelus coioides - Jiaxing Chen; Cheng Peng; Jingjun Huang; Herong Shi; Ling Xiao; Lin Tang; Haoran Lin; Shuisheng Li; Yong Zhang (Journal of Fish Biology, 2021)
Sex change in teleost fishes is commonly regulated by social factors. In species that exhibit protogynous sex change, such as the orange‐spotted grouper Epinephelus coioides , when the dominant males are removed from the social group, the most dominant female initiates sex change. The aim of this study was to determine the regulatory mechanisms of socially controlled sex change in E. coioides . We investigated the seasonal variation in social behaviours and sex change throughout the reproductive cycle of E. coioides , and defined the behaviour pattern of this fish during the establishment of a dominance hierarchy. The social behaviours and sex change in this fish were affected by season, and only occurred during the prebreeding season and breeding season. Therefore, a series of sensory isolation experiments was conducted during the breeding season to determine the role of physical, visual and olfactory cues in mediating socially controlled sex change. The results demonstrated that physical interactions between individuals in the social groups were crucial for the initiation and completion of sex change, whereas visual and olfactory cues alone were insufficient in stimulating sex change in dominant females. In addition, we propose that the steroid hormones 11‐ketotestosterone and cortisol are involved in regulating the initiation of socially controlled sex change.

Carbon isotope variations of modern soils in the eastern margin of the Tibetan Plateau and their controlling factors - Lin Qi; Yan-song Qiao; Zong-xiu Liu; Sha-sha Peng; Yu Cheng; Yan Wang; Xu-jiao Zhang; Ming-zhong Tian; Shuai-bin Yang; Wen-bin Bai (Journal of Mountain Science, 2021)

Formation and driving factors of sulfate in PM2.5 at a high-level atmospheric SO2 city of Yangquan in China - Cheng Wang; Yulong Yan; Yueyuan Niu; Rumei Li; Yang Xu; Dongmei Hu; Jing Wu; Lin Peng (Air Quality, Atmosphere & Health, 2021)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Stable isotopes reveal effects of natural drivers and anthropogenic pressures on isotopic niches of invertebrate communities in a large subtropical river of China - Sai Wang; Lin-Hui Su; Bang-Ke Luo; Ying-Jun Qin; Simon D. Stewart; Jin-Peng Tang; Tuan-Tuan Wang; Yang Yang; Gong Cheng (Environmental Science and Pollution Research, 2020)

Natural sex change in mature protogynous orange‐spotted grouper ( Epinephelus coioides ): gonadal restructuring, sex hormone shifts and gene profiles - Cheng Peng; Qing Wang; Herong Shi; Jiaxing Chen; Shuisheng Li; Huihong Zhao; Haoran Lin; Jianchun Yang; Yong Zhang (Journal of Fish Biology, 2020)
Sexual patterns of teleosts are extremely diverse and include both gonochorism and hermaphroditism. As a protogynous hermaphroditic fish, all orange‐spotted groupers ( Epinephelus coioides ) develop directly into females, and some individuals change sex to become functional males later in life. This study investigated gonadal restructuring, shifts in sex hormone levels and gene profiles of cultured mature female groupers during the first (main) breeding season of 2019 in Huizhou, China (22° 42′ 02.6″ N, 114° 32′ 10.1″ E). Analysis of gonadal restructuring revealed that females with pre‐vitellogenic ovaries underwent vitellogenesis, spawning and regression and then returned to the pre‐vitellogenic stage in the late breeding season, at which point some changed sex to become males via the intersex gonad stage. A significant decrease in the level of serum 17 β ‐estradiol (E2) was observed during ovary regression but not during sex change, whereas serum 11‐ketotestosterone (11‐KT) concentrations increased significantly during sex change with the highest concentration in newly developed males. Consistent with serum hormone changes, a significant decrease in cyp19a1a expression was observed during ovary regression but not during sex change, whereas the expression of cyp11c1 and hsd11b2 increased significantly during sex change. Interestingly, hsd11b2 but not cyp11c1 was significantly upregulated from the pre‐vitellogenic ovary stage to the early intersex gonad stage. These results suggest that a decrease in serum E2 concentration and downregulation of cyp19a1a expression are not necessary to trigger the female‐to‐male transformation, whereas increased 11‐KT concentration and upregulation of hsd11b2 expression may be key events for the initiation of sex change in the orange‐spotted grouper.

Five new ent -kaurane diterpenes from Annona squamosa L. pericarps - Ya-Yun Chen; Cheng-Yao Ma; Mao-Lin Wang; Jia-Hui Lu; Peng Hu; Jian-Wei Chen; Xiang Li; Yong Chen (Natural Product Research, 2020)

Outflow sediment concentration forecasting by integrating machine learning approaches and time series analysis in reservoir desilting operation - Ming-Jui Chang; Gwo-Fong Lin; Fong-Zuo Lee; Yi-Cheng Wang; Peng-An Chen; Ming-Chang Wu; Jihn-Sung Lai (Stochastic Environmental Research and Risk Assessment, 2020)

Short-term associations between ambient fine particulate matter pollution and hospital visits for chronic obstructive pulmonary disease in Yinzhou District, China - Cheng-yi Lin; Die Li; Jie-ming Lu; Zhe-bin Yu; Yao Zhu; Peng Shen; Meng-ling Tang; Ming-juan Jin; Hong-bo Lin; Li-ming Shui; Kun Chen; Jian-bing Wang (Environmental Science and Pollution Research, 2020)

The maize B chromosome is capable of expressing microRNAs and altering the expression of microRNAs derived from A chromosomes - Yen-Hua Huang; Shu-Fen Peng; Yao-Pin Lin; Ya-Ming Cheng (Chromosome Research, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Multiple genetic factors affecting the pharmacokinetic and pharmacodynamic processes of tacrolimus in Chinese myasthenia gravis patients - Huan-Yu Meng; Xi Li; Wan-Lin Jin; Cheng-Kai Yan; Xiao-Hua Dong; Qiu Xu; Yu-Yao Peng; Zhi-Bin Li; Yi Li; Zhao-Hui Luo; Li-Qun Xu; Huan Yang (European Journal of Clinical Pharmacology, 2020)

Nanochemoprevention with therapeutic benefits: An updated review focused on epigallocatechin gallate delivery - Qiong-Qiong Yang; Xin-Lin Wei; Ya-Peng Fang; Ren-You Gan; Min Wang; Ying-Ying Ge; Dan Zhang; Li-Zeng Cheng; Harold Corke (Critical Reviews in Food Science and Nutrition, 2020)

Mechanisms behind soil N dynamics following cover restoration in degraded land in subtropical China - Xiangzhou Zheng; Cheng Lin; Baoling Guo; Juhua Yu; Hong Ding; Shaoyun Peng; Jinbo Zhang; Eric Ireland; Deli Chen; Christoph Müller; Yushu Zhang (Journal of Soils and Sediments, 2020)

Effects of Dietary Supplementation of Recombinant Plectasin on Growth Performance, Intestinal Health and Innate Immunity Response in Broilers - Jing Lin Ma; Li Hua Zhao; Dan Dan Sun; Jing Zhang; Yong Peng Guo; Zhi Qiang Zhang; Qiu Gang Ma; Cheng Ji; Li Hong Zhao (Probiotics and Antimicrobial Proteins, 2020)

Novel B-chromosome-specific transcriptionally active sequences are present throughout the maize B chromosome - Zi-Jie Hong; Jun-Xiang Xiao; Shu-Fen Peng; Yao-Pin Lin; Ya-Ming Cheng (Molecular Genetics and Genomics, 2020)

Transient Receptor Potential Ankyrin 1 Contributes to Lysophosphatidylcholine-Induced Intracellular Calcium Regulation and THP-1-Derived Macrophage Activation - Chao Tian; Rongqi Huang; Feng Tang; Zuoxian Lin; Na Cheng; Xiaobo Han; Shuai Li; Peng Zhou; Sihao Deng; Hualin Huang; Huifang Zhao; Junjie Xu; et al. (The Journal of Membrane Biology, 2020)

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

Three new Coccomyces species from Shennongjia National Nature Reserve in China - Tu Lv; Wan-Peng Tang; Shu-Rui Cai; Cheng-Lin Hou (Mycological Progress, 2019)

Occurrence of Bryde's whales, Balaenoptera edeni , in the northern Beibu Gulf, China - Mo Chen; Shiang‐Lin Huang; Haiping Wu; Zhigang Mei; Yiwen Chen; Jingsong Zheng; Wen Cheng; Keshun Deng; Chengteng Yang; Mao Chen; Chun‐Chieh Wang; Derun Lin; et al. (Marine Mammal Science, 2019)

Adult sacrococcygeal teratoma: a retrospective study over eight years at a single institution - Xiang-ming Xu; Feng Zhao; Xiao-fei Cheng; Wei-xiang Zhong; Jing-peng Liu; Wei-qin Jiang; Xiao-kai Yu; Jian-jiang Lin (Journal of Zhejiang University-SCIENCE B, 2019)

Permanent displacement models of earthquake-induced landslides considering near-fault pulse-like ground motions - Ying-bin Zhang; Chen-lin Xiang; Yan-long Chen; Qian-gong Cheng; Li Xiao; Peng-cheng Yu; Zhi-wang Chang (Journal of Mountain Science, 2019)

Attribute recognition model for risk assessment of water inrush - Jing Wang; Shu-cai Li; Li-ping Li; Peng Lin; Zhen-hao Xu; Cheng-lu Gao (Bulletin of Engineering Geology and the Environment, 2019)

Socially controlled male‐to‐female sex reversal in the protogynous orange‐spotted grouper, Epinephelus coioides - Jiaxing Chen; Ling Xiao; Cheng Peng; Zhifeng Ye; Dengdong Wang; Yuqing Yang; Haifa Zhang; Mi Zhao; Shuisheng Li; Haoran Lin; Yong Zhang (Journal of Fish Biology, 2019)
Socially controlled sex change in teleosts is a dramatic example of adaptive reproductive plasticity. In many cases, the occurrence of sex change is triggered by a change in the social context, such as the disappearance of the dominant individual. The orange‐spotted grouper Epinephelus coioides is a typical protogynous hermaphrodite fish that changes sex from female to male and remains male throughout its life span. In this study, male‐to‐female sex reversal in male Epinephelus coioides was successfully induced by social isolation. The body length and mass, gonadal change, serum sex steroid hormone levels and sex‐related gene expression patterns during the process of socially controlled male‐to‐female sex reversal in E. coioides were systematically examined. This report investigates the physiological mechanisms of the socially controlled male‐to‐female sex reversal process in a protogynous hermaphrodite grouper species. The results enable us to study the physiological control of sex change, not only from female to male, but also from male to female.

Insights into the role of extracellular polymeric substances in Zn2+ adsorption in different biological sludge systems - Yu-Xia Song; Cheng-Hai Lu; Peng Liu; Xi-Lin Chai; Xi Chen; Xiao-Bo Min; Chong-Jian Tang; Li-Yuan Chai (Environmental Science and Pollution Research, 2018)

Triterpenoid saponins from the buds of Lonicera similis - Xiao Zhang; Li-Hua Zou; Yu-Lin He; Cheng Peng; Li Guo; Liang Xiong (Natural Product Research, 2018)

TMEM88 mediates inflammatory cytokines secretion by regulating JNK/P38 and canonical Wnt/β-catenin signaling pathway in LX-2 cells - Tao Xu; Lin-xin Pan; Yun-xuan Ge; Peng Li; Xiao-ming Meng; Cheng Huang; Jun Li (Inflammopharmacology, 2018)

Integrating CNVs into meta-QTL identified GBP4 as positional candidate for adult cattle stature - Xiu-Kai Cao; Yong-Zhen Huang; Yi-Lei Ma; Jie Cheng; Zhen-Xian Qu; Yun Ma; Yue-Yu Bai; Feng Tian; Feng-Peng Lin; Yu-Lin Ma; Hong Chen (Functional & Integrative Genomics, 2018)

A fine-grained perspective on the robustness of global cargo ship transportation networks - Peng Peng; Shifen Cheng; Jinhai Chen; Mengdi Liao; Lin Wu; Xiliang Liu; Feng Lu (Journal of Geographical Sciences, 2018)

Identifying potentially common genes between dyslipidemia and osteoporosis using novel analytical approaches - Xu Lin; Cheng Peng; Jonathan Greenbaum; Zhang-Fang Li; Ke-Hao Wu; Zeng-Xin Ao; Tong Zhang; Jie Shen; Hong-Wen Deng (Molecular Genetics and Genomics, 2018)

The Risk Assessment of Tunnels Based on Grey Correlation and Entropy Weight Method - Cheng-lu Gao; Shu-cai Li; Jing Wang; Li-ping Li; Peng Lin (Geotechnical and Geological Engineering, 2018)

Responsibility modulates the neural correlates of regret during the sequential risk-taking task - Lin Li; Zhiyuan Liu; Huanghuang Niu; Li Zheng; Xuemei Cheng; Peng Sun; Fanzhi Anita Zhou; Xiuyan Guo (Experimental Brain Research, 2018)

Modulation of financial deprivation on deception and its neural correlates - Peng Sun; Xiaoli Ling; Li Zheng; Jia Chen; Lin Li; Zhiyuan Liu; Xuemei Cheng; Xiuyan Guo (Experimental Brain Research, 2017)

Tide- and wind-driven variability of water level in Sansha Bay, Fujian, China - Hongyang Lin; Jianyu Hu; Jia Zhu; Peng Cheng; Zhaozhang Chen; Zhenyu Sun; Dewen Chen (Frontiers of Earth Science, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Overexpression of the ascorbate peroxidase gene from eggplant and sponge gourd enhances flood tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Chiu-Chen Chen; Shi-Peng Chen; Kuan-Hung Lin; Li-Ru Chen; Yu-Huei Su; His-Cheng Yen (Journal of Plant Research, 2017)

Branched polymeric prodrug/programmed cell death 4 complexes for combinational cancer therapy - Yu-Jing He; Lei Xing; Peng-Fei Cui; Jia-Liang Zhang; Jian-Bin Qiao; Cheng-Qiong Luo; Ge Jiang; Hu-Lin Jiang (Journal of Pharmaceutical Investigation, 2017)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

The P450 oxidoreductase (POR) rs2868177 and cytochrome P450 (CYP) 2B6*6 polymorphisms contribute to the interindividual variability in human CYP2B6 activity - Li-chen Gao; Fang-qun Liu; Li Yang; Lin Cheng; Hai-ying Dai; Ran Tao; Shi-Peng Cao; Di Wang; Jie Tang (European Journal of Clinical Pharmacology, 2016)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

SSR-based genetic mapping and QTL analysis for timing of spring bud flush, young shoot color, and mature leaf size in tea plant (Camellia sinensis) - Li-Qiang Tan; Li-Yuan Wang; Li-Yi Xu; Li-Yun Wu; Min Peng; Cheng-Cai Zhang; Kang Wei; Pei-Xian Bai; Hai-Lin Li; Hao Cheng; Gui-Nian Qi (Tree Genetics & Genomes, 2016)

Microsatellite analysis of the genetic relationships between wild and cultivated giant grouper in the South China Sea - QING WANG; XIANG WANG; ZHENZHEN XIE; YIQI LI; LING XIAO; CHENG PENG; HAIFA ZHANG; SHUISHENG LI; YONG ZHANG; HAORAN LIN (Journal of Genetics, 2016)

Cytomolecular characterization and origin of de novo formed maize B chromosome variants - Ya-Ming Cheng; Ying-Ru Feng; Yao-Pin Lin; Shu-Fen Peng (Chromosome Research, 2016)

Metabolic differences of industrial acarbose-producing Actinoplanes sp. A56 under various osmolality levels - Kun-tai Li; Wei-fu Peng; Wei Xia; Lin Huang; Xin Cheng (World Journal of Microbiology and Biotechnology, 2016)

Preparation and Effect of Lighting on Structures and Properties of GSH Capped ZnSe QDs - Ling Ding; Zeze Peng; Peijiang Zhou; Gary J. Cheng; Qiong Nian; Dong Lin; Jinhui Zhou; Yuhe Liang (Journal of Fluorescence, 2015)

Health risk assessment of toxic VOCs species for the coal fire well drillers - Yulong Yan; Lin Peng; Na Cheng; Huiling Bai; Ling Mu (Environmental Science and Pollution Research, 2015)

Isolation and sequence analysis of a canine distemper virus from a raccoon dog in Jilin Province, China - Yuening Cheng; Jianke Wang; Miao Zhang; Jianjun Zhao; Xiqun Shao; Zengjun Ma; Hang Zhao; Peng Lin; Hua Wu (Virus Genes, 2015)

The Effects of Simazine, a Chlorotriazine Herbicide, on the Expression of Genes in Developing Male Xenopus laevis - Linlin Sai; Yanzhong Liu; Binpeng Qu; Gongchang Yu; Qiming Guo; Cunxiang Bo; Lin Xie; Qiang Jia; Yuezhong Li; Xiangxin Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Transcriptional regulation of the iac locus from Acinetobacter baumannii by the phytohormone indole-3-acetic acid - Hung-Yu Shu; Ling-Chun Lin; Tze-Kang Lin; Hao-Ping Chen; Hsueh-Hui Yang; Kou-Cheng Peng; Guang-Huey Lin (Antonie van Leeuwenhoek, 2015)

Characterization of four B-chromosome-specific RAPDs and the development of SCAR markers on the maize B-chromosome - Kuo-Wei Kao; Chien-Yu Lin; Shu-Fen Peng; Ya-Ming Cheng (Molecular Genetics and Genomics, 2015)

Cloning of a caffeoyl-coenzyme A O-methyltransferase from Camellia sinensis and analysis of its catalytic activity - Yue Zhang; Hai-peng Lv; Cheng-ying Ma; Li Guo; Jun-feng Tan; Qun-hua Peng; Zhi Lin (Journal of Zhejiang University-SCIENCE B, 2015)

Conjugated linoleic acid alters growth performance, tissue lipid deposition, and fatty acid composition of darkbarbel catfish (Pelteobagrus vachelli) - Gui-Fang Dong; Wen-Zuo Liu; Lin-Zhou Wu; Deng-hang Yu; Feng Huang; Peng-Cheng Li; Yan-ou Yang (Fish Physiology and Biochemistry, 2015)

Assessing Atrazine-Induced Toxicities in Bufo bufo gargarizans Cantor - Linlin Sai; Qingbo Wu; Binpeng Qu; Cunxiang Bo; Gongchang Yu; Qiang Jia; Lin Xie; Yuezhong Li; Qiming Guo; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Bioaugmentation of a sequencing batch biofilm reactor with Comamonas testosteroni and Bacillus cereus and their impact on reactor bacterial communities - Zhongqin Cheng; Mei Chen; Liqun Xie; Lin Peng; Maohua Yang; Mengying Li (Biotechnology Letters, 2015)

Overexpression of a maize WRKY58 gene enhances drought and salt tolerance in transgenic rice - Ronghao Cai; Yang Zhao; Yufu Wang; Yongxiang Lin; Xiaojian Peng; Qian Li; Yuwei Chang; Haiyang Jiang; Yan Xiang; Beijiu Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

Posttreatment with propofol attenuates lipopolysaccharide-induced up-regulation of inflammatory molecules in primary microglia - Mian Peng; Ji-Shi Ye; Yan-Lin Wang; Chang Chen; Cheng-Yao Wang (Inflammation Research, 2014)

Genome expression profile analysis of the maize sheath in response to inoculation to R. solani - Jian Gao; Zhe Chen; Mao Luo; Hua Peng; Haijian Lin; Cheng Qin; Guangsheng Yuan; Yaou Shen; Haiping Ding; Maojun Zhao; Guangtang Pan; Zhiming Zhang (Molecular Biology Reports, 2014)

Aroma changes of black tea prepared from methyl jasmonate treated tea plants - Jiang Shi; Li Wang; Cheng-ying Ma; Hai-peng Lv; Zong-mao Chen; Zhi Lin (Journal of Zhejiang University-SCIENCE B, 2014)

HOXA9 Gene Expression in Acute Myeloid Leukemia - De-Peng Li; Zhen-Yu Li; Wei Sang; Hai Cheng; Xiu-Ying Pan; Kai-Lin Xu (Cell Biochemistry and Biophysics, 2013)

An Informetric Profile of Water Resources Management Literatures - Jun-Lin Ren; Peng-Hui Lyu; Xin-Mu Wu; Fei-Cheng Ma; Zhi-Zhang Wang; Gang Yang (Water Resources Management, 2013)

Hesperetin protects against cardiac remodelling induced by pressure overload in mice - Wei Deng; Duan Jiang; Yi Fang; Heng Zhou; Zhihong Cheng; Yafen Lin; Rui Zhang; Jieyu Zhang; Peng Pu; Yuan Liu; Zhouyan Bian; Qizhu Tang (Journal of Molecular Histology, 2013)

Niche Divergence Among Sex and Age Classes in Black-and-White Snub-nosed Monkeys (Rhinopithecus bieti) - Yi Wan; Rui-Chang Quan; Guo-Peng Ren; Lin Wang; Yong-Cheng Long; Xiao-Hu Liu; Jian-Guo Zhu (International Journal of Primatology, 2013)

Effects of extracellular calcium on viability and osteogenic differentiation of bone marrow stromal cells in vitro - Shaowen Cheng; Wei Wang; Zhongqin Lin; Ping Zhou; Xiaolei Zhang; Wei Zhang; Qingyu Chen; Dongquan Kou; Xiaozhou Ying; Yue Shen; Xiaojie Cheng; Ziming Yu; et al. (Human Cell, 2013)

Warnstorfia exannulata, an aquatic moss in the Arctic: seasonal growth responses - Cai-Qing Guo; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Yi-Feng Yao; Lin-Gen Bian; Su-Ping Li; Cheng-Sen Li (Climatic Change, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Potential hazard analysis and risk assessment of debris flow by fuzzy modeling - Jeng-Wen Lin; Cheng-Wu Chen; Cheng-Yi Peng (Natural Hazards, 2012)

Experimental Investigation on the Filtering Flow Law of Pre-gelled Particle in Porous Media - Jing Wang; Hui-qing Liu; Zeng-lin Wang; Peng-cheng Hou (Transport in Porous Media, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

Genome-wide analysis of Aux/IAA gene family in Solanaceae species using tomato as a model - Jian Wu; Zhen Peng; Songyu Liu; Yanjun He; Lin Cheng; Fuling Kong; Jie Wang; Gang Lu (Molecular Genetics and Genomics, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

Kalman filter decision systems for debris flow hazard assessment - Jeng-Wen Lin; Cheng-Wu Chen; Cheng-Yi Peng (Natural Hazards, 2012)

Nicotine promotes proliferation and collagen synthesis of chondrocytes isolated from normal human and osteoarthritis patients - Xiaozhou Ying; Shaowen Cheng; Yue Shen; Xiaojie Cheng; Ferdinand An Rompis; Wei Wang; Zhongqin Lin; Qingyu Chen; Wei Zhang; Dongquan Kou; Lei Peng; Xin Qiao Tian; et al. (Molecular and Cellular Biochemistry, 2012)

Effect of Boron on Osteogenic Differentiation of Human Bone Marrow Stromal Cells - Xiaozhou Ying; Shaowen Cheng; Wei Wang; Zhongqin Lin; Qingyu Chen; Wei Zhang; Dongquan Kou; Yue Shen; Xiaojie Cheng; Ferdinand An Rompis; Lei Peng; Chuan zhu Lu (Biological Trace Element Research, 2011)

Identification, isolation and expression analysis of auxin response factor (ARF) genes in Solanum lycopersicum - Jian Wu; Feiyan Wang; Lin Cheng; Fuling Kong; Zhen Peng; Songyu Liu; Xiaolin Yu; Gang Lu (Plant Cell Reports, 2011)

Quantitative Analysis of Quercetin in Euphorbia helioscopia L by RP-HPLC - Hai Peng Liu; Xiao Feng Shi; You Cheng Zhang; Zhong Xin Li; Lin Zhang; Zhe Yuan Wang (Cell Biochemistry and Biophysics, 2011)

Identification and characterization of Sox genes in the silkworm, Bombyx mori - Ling Wei; Daojun Cheng; Dong Li; Meng Meng; Lina Peng; Lin Tang; Minhui Pan; Zhonghuai Xiang; Qingyou Xia; Cheng Lu (Molecular Biology Reports, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Establishment of a cerebral schistosomiasis experimental model in rabbits - Peng Wang; Dan Wang; Shi-Jie Chen; Ming-Can Wu; Xiang-Lin Cheng; Jun-Chuan Li; Ting-Xuan Chen; Zhan-Sheng Zhu (Neuroscience Bulletin, 2011)

Artesunate inhibits growth and induces apoptosis in human osteosarcoma HOS cell line in vitro and in vivo - Qiang Xu; Zhao-xu Li; Hui-qin Peng; Zheng-wang Sun; Rui-lin Cheng; Zhao-ming Ye; Wei-xu Li (Journal of Zhejiang University-SCIENCE B, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Angiotensin-converting enzyme 2 (ACE2) proteins of different bat species confer variable susceptibility to SARS-CoV entry - Yuxuan Hou; Cheng Peng; Meng Yu; Yan Li; Zhenggang Han; Fang Li; Lin-Fa Wang; Zhengli Shi (Archives of Virology, 2010)

Personalized image-based templates for precise acetabular prosthesis placement in total hip arthroplasty: a pilot study - Bin Chen; Sheng-xiang Xiao; Peng-cheng Gu; Xiang-jin Lin (Journal of Zhejiang University-SCIENCE B, 2010)

Danshen protects endothelial progenitor cells from oxidized low-density lipoprotein induced impairment - Kang-ting Ji; Jun-de Chai; Cheng Xing; Jin-liang Nan; Peng-lin Yang; Ji-fei Tang (Journal of Zhejiang University-SCIENCE B, 2010)

Role of mast cells, stem cell factor and protease-activated receptor-2 in tubulointerstitial lesions in IgA nephropathy - Hong Liu; Fuyou Liu; Youming Peng; Yinghong Liu; Lingyan Li; Xiwen Tu; Meichu Cheng; Xiangqing Xu; Xing Chen; Guanghui Ling; Lin Sun (Inflammation Research, 2010)

Responses of phospholipase D and lipoxygenase to mechanical wounding in postharvest cucumber fruits - Yu-ying Zhao; Chun-lu Qian; Ji-cheng Chen; Yan Peng; Lin-chun Mao (Journal of Zhejiang University-SCIENCE B, 2010)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Estimating Long-Term Changes in China’s Village Landscapes - Erle Christopher Ellis; Nagaraj Neerchal; Kui Peng; Hong Sheng Xiao; Hongqing Wang; Yan Zhuang; Shou Cheng Li; Jun Xi Wu; Jia Guo Jiao; Hua Ouyang; Xu Cheng; Lin Zhang Yang (Ecosystems, 2009)

An analytical algorithm with a wave age factor for altimeter wind speed retrieval - Yongcun Cheng; Qing Xu; Yuguang Liu; Hui Lin; Peng Xiu; Xiaobin Yin; Haibo Zong; Zengrui Rong (International Journal of Remote Sensing, 2008)

Salinicoccus salitudinis sp. nov., a new moderately halophilic bacterium isolated from a saline soil sample - Yi-Guang Chen; Xiao-Long Cui; Wen-Jun Li; Li-Hua Xu; Meng-Liang Wen; Qian Peng; Cheng-Lin Jiang (Extremophiles, 2008)

Apoptosis induced by ardipusilloside III through BAD dephosphorylation and cleavage in human glioblastoma U251MG cells - Hong Lin; Xiang Zhang; Guang Cheng; Hai-Feng Tang; Wei Zhang; Hai-Ning Zhen; Jin-Xiang Cheng; Bo-Lin Liu; Wei-Dong Cao; Wen-Peng Dong; Peng Wang (Apoptosis, 2008)

Streptomyces tritolerans sp. nov., a novel actinomycete isolated from soil in Karnataka, India - Dastager G. Syed; Dayanand Agasar; Chang-Jin Kim; Wen-Jun Li; Jae-Chan Lee; Dong-Jin Park; Li-Hua Xu; Xin-Peng Tian; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Polymorphism for Transforming Growth Factor Beta 1-509 (TGF-B1-509): Association with Endometriosis - Yao-Yuan Hsieh; Chi-Chen Chang; Fuu-Jen Tsai; Ching-Tien Peng; Lian-Shun Yeh; Cheng-Chieh Lin (Biochemical Genetics, 2005)

Daily changes in components of xanthophyll cycle and antioxidant systems in leaves of rice at different developing stage - Cheng-Wei Yang; Yi-Zhu Chen; Chang-Lian Peng; Duan Jun; Gui-Zhu Lin (Acta Physiologiae Plantarum, 2001)